Laminated window for infrared sensing system

By using the window of the asymmetric layer of pressure structure in the LIDAR system, the problem of impact windows is susceptible to damage, the higher impact performance and optical transmission characteristics are achieved, and the effectiveness of the system is improved.

CN119343234APending Publication Date: 2025-01-21CORNING INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380045655.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-06-02
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Impact windows in existing LIDAR systems are susceptible to scratches and damage from rocks and other objects, causing the windows to scatter electromagnetic radiation, weakening the effectiveness of the system.

Method used

Windows with asymmetric layer pressure structures include the first glass mezzanine, the second glass mezzanine, and the middle layer. The first glass expansion is not strengthened.

Benefits of technology

Improve the impact performance and optical transmission characteristics of the window, reduce the scattering of electromagnetic radiation, and enhance the effectiveness of the LIDAR system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343234A_ABST
    Figure CN119343234A_ABST
Patent Text Reader

Abstract

A window including an asymmetric laminate structure for a sensing system is disclosed. The asymmetric laminate structure includes a first glass interlayer, a second glass interlayer, and an intermediate layer coupling the first glass interlayer to the second glass interlayer. The first glass interlayer is at least twice thicker than the second glass interlayer and is strengthened to a smaller extent than the second glass interlayer such that the first glass interlayer includes a central tension in its central region that is less than a central tension of the second glass interlayer. The intermediate layer comprises an average optical transmittance greater than or equal to 98% throughout a 50 nm wavelength range of interest comprised in the 800 nm to 1800 nm wavelength range.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] priority

[0002] This application claims priority under the U.S. Patent Act to U.S. Provisional Application Serial No. 63 / 349,764 filed on June 7, 2022, the contents of which are relied upon and incorporated herein by reference in their entirety. Background Art

[0003] A LIDAR (light detection and ranging) system includes an electromagnetic radiation transmitter and a sensor. The electromagnetic radiation transmitter emits electromagnetic radiation, which can be reflected from an object and detected by a sensor. The electromagnetic radiation can be pulsed or otherwise distributed across a radial range to detect objects across a field of view. Information about the object can be decrypted from the characteristics of the detected reflected electromagnetic radiation. The distance of the object from the electromagnetic radiation can be determined based on the flight time from the emission of the electromagnetic radiation to the detection of the reflected electromagnetic radiation. If the object is moving, the path and speed of the object can be determined based on the radial position of the reflected and detected emitted electromagnetic radiation based on time-varying offsets and Doppler frequency measurements.

[0004] LIDAR systems in automobiles and other infrared sensing systems in exposed environments, such as aerospace or home security applications, need to be protected from the environment and various sources of damage, such as with a shield lens or a shield glass window. Vehicles are another potential application for LIDAR systems, where the LIDAR system provides spatial imaging capabilities to achieve assisted semi-autonomous or fully autonomous driving. In such applications, electromagnetic radiation emitters and sensors are mounted on the roof of the vehicle or on the low front portion of the vehicle. For vehicle LIDAR applications, electromagnetic radiation emitters that emit electromagnetic radiation with wavelengths outside the visible light range (such as at 905nm or 1550nm) are considered. In order to protect the electromagnetic radiation emitter and sensor from impacts of rocks and other objects, a window is placed between the electromagnetic radiation emitter and sensor and the external environment within the line of sight of the electromagnetic radiation emitter and sensor. For other applications of LIDAR systems, such as aerospace and home security applications, a window is similarly placed between the electromagnetic radiation emitter / sensor and the external environment. However, there is a problem in that rocks and other objects impacting the window can scratch the window and cause other types of damage to it, which causes the window to scatter emitted and reflected electromagnetic radiation, thereby reducing the effectiveness of the LIDAR system. Summary of the invention

[0005] The present disclosure solves this problem with a window having an asymmetric laminate structure that also provides suitable optical performance in the wavelength range of interest associated with a sensing system. The window includes a first glass interlayer forming an exterior surface of the window facing the external environment, a second glass interlayer forming an interior surface of the window facing components of the sensing system (e.g., emitters and sensors), and an interlayer coupling the first glass interlayer to the second glass interlayer. The first glass interlayer is generally strengthened (e.g., thermally, mechanically, chemically) to a lesser extent than the second glass interlayer (e.g., the first glass interlayer may not be strengthened), so that the first glass interlayer generally includes a central tension less than the central tension of the second glass interlayer to resist crack propagation. The first glass interlayer includes a first thickness greater than a second thickness associated with the second glass interlayer to improve impact resistance. The second glass interlayer may be chemically strengthened to help maintain airtightness in the event that an impact generates a crack (e.g., a crack, a cavity, a void) extending through the first glass interlayer. The interlayer is selected to adhere the first glass interlayer to the second glass interlayer with sufficient durability while also providing a relatively high optical transmittance in a wavelength range of interest associated with the sensing system. In an embodiment, the wavelength range of interest comprises a 50 nm wavelength range of interest contained within the 800 nm to 1800 nm wavelength range. The laminations described herein provide improved impact performance over certain existing monolithic window structures while also having the optical transmittance characteristics required for sensor applications.

[0006] Aspect (1) of the present disclosure relates to a window for a sensing system, comprising: a first glass interlayer, the first glass interlayer comprising a first major surface, a second major surface opposite to the first major surface, and a first thickness extending between the first major surface and the second major surface; a second glass interlayer, the second glass interlayer comprising a third major surface, a fourth major surface opposite to the third major surface, and a second thickness extending between the third major surface and the fourth major surface; an intermediate layer, the intermediate layer disposed between the first glass interlayer and the second glass interlayer and bonding the second major surface to the third major surface; and one or more layered films disposed on at least one of the first major surface and the fourth major surface, each of the one or more layered films comprising alternating layers of one or more higher refractive index materials and one or more lower refractive index materials, wherein: for light normally incident on the fourth major surface or the first major surface, The interlayer alone comprises an average transmittance greater than 98% over a 50 nm wavelength range of interest, the 50 nm wavelength range of interest being comprised within a wavelength range of 800 nm to 1800 nm, the alternating layers of the one or more layered films being configured such that for light normally incident on the first major surface or the fourth major surface, the window exhibits an average transmittance greater than or equal to 95% over the 50 nm wavelength range of interest, the alternating layers of the one or more layered films being configured such that for light normally incident on the first major surface or the fourth major surface, the window exhibits an average reflectivity less than or equal to 5% over the 50 nm wavelength range of interest, the first thickness is at least twice the second thickness, and the second glass interlayer is strengthened to a greater extent than the first glass interlayer such that the second glass interlayer exhibits a central tension in a central region thereof that is greater than a central tension of the first glass interlayer.

[0007] Aspect (2) of the present disclosure relates to the window as described in aspect (1), wherein the first glass interlayer is not strengthened.

[0008] Aspect (3) of the present disclosure relates to the window as described in any of the preceding aspects, wherein: the first thickness is greater than or equal to 2.0 mm and less than or equal to 8.0 mm, and the second thickness is greater than or equal to 0.1 mm and less than or equal to 1.2 mm.

[0009] Aspect (4) of the present disclosure relates to the window as described in any of the preceding aspects, wherein both the first glass interlayer and the second glass interlayer are formed of aluminosilicate glass.

[0010] Aspect (5) of the present disclosure relates to the window as described in any one of aspects (1) to (3), wherein the first glass interlayer is formed of a glass that exhibits abnormal fracture behavior when subjected to a Vickers indenter test.

[0011] Aspect (6) of the present disclosure relates to the window as described in aspect (5), wherein the first glass interlayer comprises a borosilicate glass composition.

[0012] Aspect (7) of the present disclosure relates to the window as described in aspect (6), wherein: in terms of constituent oxides, the borosilicate glass composition comprises: SiO2, B2O3, Al2O3, one or more alkali metal oxides and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO and ZnO, greater than or equal to 11 mol% and less than or equal to 16 mol% of B2O3, greater than or equal to 2 mol% and less than or equal to 6 mol% of Al2O3, and greater than or equal to 7.0 mol% of Na2O, K2O, MnO, and the like. The total amount of gO and CaO, the molar percentage concentration based on SiO2, B2O3, the one or more alkali metal oxides, Al2O3 and the one or more alkaline earth metal oxides satisfies the following relationship: (R2O+R'O)≥Al2O3, 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, and wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides.

[0013] Aspect (8) of the present disclosure relates to the window as described in any of the preceding aspects, wherein the first thickness is at least 3 times the second thickness.

[0014] Aspect (9) of the present disclosure relates to the window as described in any of the preceding aspects, wherein the second glass interlayer is chemically strengthened so that the second glass interlayer comprises a surface compressive stress greater than or equal to 250 MPa and less than or equal to 900 MPa at the fourth major surface.

[0015] Aspect (10) of the present disclosure relates to the window of aspect (9), wherein when the first glass interlayer is subjected to a 1g ball bearing impact traveling at 160.93 km / hr, a crack extending through the entire second thickness is not formed.

[0016] Aspect (11) of the present disclosure relates to the window as described in any of the preceding aspects, wherein the intermediate layer comprises an optically clear adhesive or a UV curable acrylate resin.

[0017] Aspect (12) of the present disclosure relates to the window as described in aspect (11), wherein the intermediate layer comprises a third thickness greater than or equal to 0.05 mm and less than or equal to 1.0 mm.

[0018] Aspect (13) of the present disclosure relates to the window as described in any one of aspects (1)-(12), wherein the 50 nm wavelength range of interest is centered at a wavelength between 900 nm and 950 nm.

[0019] Aspect (14) of the present disclosure relates to the window as described in any one of aspects (1)-(12), wherein the 50 nm wavelength range of interest is centered at a wavelength between 1525 nm and 1575 nm.

[0020] Aspect (15) of the present disclosure relates to a window as described in any of the preceding aspects, wherein: the one or more layered films include a first layered film disposed on the first major surface, and the window includes a maximum hardness of at least 8 GPa at the first layered film and measured by a Bosch indenter hardness test.

[0021] Aspect (16) of the present disclosure relates to a window as described in aspect (15), wherein: the one or more layered films include a second layered film disposed on the fourth major surface, and the quantity, thickness, number and material of the alternating layers of the first layered film and the second layered film are combined so that: for light incident on the first surface and the second surface at an angle less than or equal to 15°, the window has an average reflectivity of less than 0.5% calculated over the 50 nm wavelength range of interest between 1400 nm and 1600 nm; for an incident angle of less than or equal to 60° on the first layered film, the window has a CIELAB L* value less than or equal to 45; and when viewed from a side of the first layered film, the window has CIELAB a* and b* values ​​greater than or equal to -6.0 and less than or equal to 6.0.

[0022] Aspect (17) of the present disclosure relates to a window as described in aspect (16), wherein: one of the alternating layers of the first layered film that is farthest from the first major surface forms a terminal surface material of the window, the terminal surface material of the window includes the lower refractive index material, and the first layered film includes a scratch-resistant layer formed from one of the one or more higher refractive index materials and having a thickness greater than or equal to 1500nm and less than or equal to 5000nm.

[0023] Aspect (18) of the present disclosure relates to a window as described in aspect (17), wherein: the scratch-resistant layer is separated from the terminal surface by multiple alternating layers of the one or more lower refractive index materials and the one or more higher refractive index materials of the first layered film, and the scratch-resistant layer is separated from the terminal surface by at least 1000 nm.

[0024] Aspect (19) of the present disclosure relates to a window as described in aspect (15), wherein: the one or more layered films include a second layered film disposed on the fourth major surface, and the number, thickness and material of the alternating layers of the first layered film and the second layered film are configured so that: for light incident on the first surface and the second surface at an incident angle less than or equal to 15°, the window has an average percent transmittance greater than 90% calculated within the 50nm wavelength range of interest; for light incident on the first surface and the second surface at an angle less than or equal to 15°, the window has an average reflectivity less than 0.5% calculated within the 50nm wavelength range of interest; and for light incident on the first surface and the second surface at an incident angle less than or equal to 15°, the window has an average percent transmittance greater than 80% calculated from 400nm to 700nm.

[0025] Aspect (20) of the present disclosure relates to a window for a sensing system, comprising: a first glass interlayer, the first glass interlayer comprising a first major surface, a second major surface opposite to the first major surface, and a first thickness extending between the first major surface and the second major surface; a second glass interlayer, the second glass interlayer comprising a third major surface, a fourth major surface opposite to the third major surface, and a second thickness extending between the third major surface and the fourth major surface; an intermediate layer, the intermediate layer being disposed between the first glass interlayer and the second glass interlayer and bonding the second major surface to the third major surface; and one or more layered films, the one or more layered films being disposed on at least one of the first major surface and the fourth major surface, each of the one or more layered films comprising alternating layers of one or more higher refractive index materials and one or more lower refractive index materials, wherein: the first glass interlayer, the second glass interlayer, and the intermediate layer are combined, without the The one or more layered films include an average transmittance greater than 90% within a 50nm wavelength range of interest, the 50nm wavelength range of interest being included in a wavelength range of 800nm ​​to 1800nm, the alternating layers of the one or more layered films are configured such that for light normally incident on the first major surface or the fourth major surface, the window exhibits an average transmittance greater than or equal to 95% within the 50nm wavelength range of interest, the alternating layers of the one or more layered films are configured such that for light normally incident on the first major surface or the fourth major surface, the window exhibits an average reflectivity less than or equal to 5% within the 50nm wavelength range of interest, the first thickness is at least twice the second thickness, and the second glass interlayer is strengthened to a greater extent than the first glass interlayer so that the second glass interlayer exhibits a central tension in a central region thereof that is greater than a central tension of the first glass interlayer.

[0026] Aspect (21) of the present disclosure relates to the window as described in aspect (20), wherein the first glass interlayer is not strengthened.

[0027] Aspect (22) of the present disclosure relates to a window as described in any of aspects (20)-(21), wherein the first thickness is greater than or equal to 2.0 mm and less than or equal to 8.0 mm, and the second thickness is greater than or equal to 0.1 mm and less than or equal to 1.2 mm.

[0028] Aspect (23) of the present disclosure relates to the window as described in any one of aspects (20)-(22), wherein both the first glass interlayer and the second glass interlayer are formed of aluminosilicate glass.

[0029] Aspect (24) of the present disclosure relates to the window as described in any one of aspects (20)-(23), wherein the first glass interlayer is formed of a glass that exhibits abnormal fracture behavior when subjected to a Vickers indenter test.

[0030] Aspect (25) of the present disclosure relates to the window as described in aspect (24), wherein the first glass interlayer comprises a borosilicate glass composition.

[0031] Aspect (26) of the present disclosure relates to the window as described in aspect (25), wherein: in terms of constituent oxides, the borosilicate glass composition comprises: SiO2, B2O3, Al2O3, one or more alkali metal oxides and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO and ZnO, greater than or equal to 11 mol% and less than or equal to 16 mol% of B2O3, greater than or equal to 2 mol% and less than or equal to 6 mol% of Al2O3, and greater than or equal to 7.0 mol% of Na2O, K2O, The total amount of MgO and CaO, based on the molar percentage concentration of SiO2, B2O3, the one or more alkali metal oxides, Al2O3 and the one or more alkaline earth metal oxides, satisfies the following relationship: (R2O+R'O)≥A12O3, and 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides.

[0032] Aspect (27) of the present disclosure relates to the window as described in any one of aspects (20)-(26), wherein the first thickness is at least 3 times the second thickness.

[0033] Aspect (28) of the present disclosure relates to a window as described in any of aspects (20)-(27), wherein the second glass interlayer is chemically strengthened so that the second glass interlayer comprises a surface compressive stress greater than or equal to 250 MPa and less than or equal to 900 MPa at the fourth major surface.

[0034] Aspect (29) of the present disclosure relates to the window of aspect (28), wherein when the first glass interlayer is subjected to a 1g ball bearing impact traveling at 160.93 km / hr, a crack extending through the entire second thickness is not formed.

[0035] Aspect (30) of the present disclosure relates to the window as described in any one of aspects (20)-(29), wherein the intermediate layer comprises an optically clear adhesive or a UV-curable acrylate resin.

[0036] Aspect (31) of the present disclosure relates to the window as described in aspect (30), wherein the intermediate layer comprises a third thickness greater than or equal to 0.05 mm and less than or equal to 1.0 mm.

[0037] Aspect (32) of the present disclosure relates to the window as described in any of aspects (20)-(31), wherein the 50 nm wavelength range of interest is centered at a wavelength between 900 nm and 950 nm.

[0038] Aspect (33) of the present disclosure relates to a window as described in any of aspects (20)-(31), wherein the 50 nm wavelength range of interest is centered at a wavelength between 1525 nm and 1575 nm.

[0039] Aspect (34) of the present disclosure relates to a window as described in any of aspects (20)-(33), wherein: the one or more layered films include a first layered film disposed on the first major surface, and the window includes a maximum hardness of at least 8 GPa at the first layered film and measured by a Bosch indenter hardness test.

[0040] Aspect (35) of the present disclosure relates to a window as described in aspect (34), wherein: the one or more layered films include a second layered film disposed on the fourth major surface, and the quantity, thickness, number and material of the alternating layers of the first layered film and the second layered film are configured so that: for light incident on the first surface and the second surface at an angle less than or equal to 15°, the window has an average reflectivity of less than 0.5% calculated over the 50 nm wavelength range of interest between 1400 nm and 1600 nm; for an incident angle of less than or equal to 60° on the first layered film, the window has a CIELAB L* value less than or equal to 45; and when viewed from one side of the first layered film, the window has CIELAB a* and b* values ​​greater than or equal to -6.0 and less than or equal to 6.0.

[0041] Aspect (36) of the present disclosure relates to a window as described in aspect (35), wherein: one of the alternating layers of the first layered film that is farthest from the first major surface forms a terminal surface material of the window, the terminal surface material of the window includes the lower refractive index material, and the first layered film includes a scratch-resistant layer formed from one of the one or more higher refractive index materials and having a thickness greater than or equal to 1500nm and less than or equal to 5000nm.

[0042] Aspect (37) of the present disclosure relates to a window as described in aspect (36), wherein: the scratch-resistant layer is separated from the terminal surface by multiple alternating layers of the one or more lower refractive index materials and the one or more higher refractive index materials of the first layered film, and the scratch-resistant layer is separated from the terminal surface by at least 1000 nm.

[0043] Aspect (38) of the present disclosure relates to a window as described in aspect (34), wherein: the one or more layered films include a second layered film disposed on the fourth major surface, and wherein the number, thickness and material of the alternating layers of the first layered film and the second layered film are configured so that: for light incident on the first surface and the second surface at an incident angle less than or equal to 15°, the window has an average percent transmittance greater than 90% calculated within the 50nm wavelength range of interest; for light incident on the first surface and the second surface at an angle less than or equal to 15°, the window has an average reflectivity less than 0.5% calculated within the 50nm wavelength range of interest; and for light incident on the first surface and the second surface at an incident angle less than or equal to 15°, the window has an average percent transmittance greater than 80% calculated from 400nm to 700nm.

[0044] Aspect (39) of the present disclosure relates to a sensor system comprising: an emitter that emits radiation within a 50 nm wavelength range of interest, the 50 nm wavelength range of interest being included in a wavelength range from 800 nm to 1800 nm; a sensor configured to detect the radiation emitted by the emitter; a housing that defines a sensor cavity, wherein the emitter and the sensor are housed in the sensor cavity; and a window as described in any of aspects (21)-(38), wherein the window is attached to the housing to hermetically seal the sensor cavity.

[0045] Aspect (40) of the present disclosure relates to a sensor system as described in aspect (39), wherein the second glass interlayer comprises a dimension larger than a dimension of the first glass interlayer, and the second glass interlayer is attached to the housing so that the first major surface is flush with a front surface of the housing.

[0046] Aspect (41) of the present disclosure relates to the sensor system of aspect (40), wherein the sensor cavity remains hermetically sealed after the window is impacted with a 1g ball bearing traveling at 160.9s km / hr at an incident angle of 45°.

[0047] Additional features and advantages will be set forth in the detailed description which follows, and in part will be readily apparent to those skilled in the art from that description or will be recognized by practicing the embodiments as described herein, including the detailed description which follows, the claims, and the accompanying drawings.

[0048] It should be understood that both the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding of the specification and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate one or more embodiments and, together with the description, serve to explain the principles and operation of the various embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is a side view of a vehicle in an external environment illustrating a LIDAR system located on a roof of the vehicle and another LIDAR system located on a front portion of the vehicle according to one or more embodiments of the present disclosure;

[0050] Figure 2 According to one or more embodiments of the present disclosure Figure 1 A schematic diagram of one of the LIDAR systems of exemplarily illustrating an electromagnetic radiation emitter and a sensor located in a housing and emitting electromagnetic radiation that exits the housing through a window and returns through the window as reflected radiation;

[0051] Figure 3A According to one or more embodiments of the present disclosure Figure 2 The area III of Figure 2 sectional view of a window illustrating a window including a substrate having a layered film on a first surface of the substrate and a second layered film on a second surface of the substrate;

[0052] Figure 3B According to one or more embodiments of the present disclosure Figure 3A The line 3A-3A is intercepted Figure 3A A cross-sectional view of a substrate of a window, the substrate comprising a first glass interlayer, a second glass interlayer and an intermediate layer;

[0053] Figure 4 According to one or more embodiments of the present disclosure Figure 3A 3, taken at region IV, illustrating a layered film comprising alternating layers of one or more higher refractive index materials and one or more lower refractive index materials, wherein the one or more layers of lower refractive index materials provide a terminal surface closest to the external environment;

[0054] Figure 5 According to one or more embodiments of the present disclosure Figure 3A 3 taken at region V, illustrating a second layered film comprising alternating layers of one or more higher refractive index materials and one or more lower refractive index materials, wherein the one or more layers of lower refractive index materials provide terminal surfaces proximate to the electromagnetic radiation emitter and sensor;

[0055] Fig. 6A is an image of a monolithic window composed of borosilicate glass after being struck by a ball bearing according to one or more embodiments of the present disclosure;

[0056] Figure 6B is an image of an asymmetric laminated window including a non-reinforced second glass interlayer after being impacted by a ball bearing according to one or more embodiments of the present disclosure;

[0057] Figure 6C is an image of an asymmetric laminated window including a chemically strengthened second glass interlayer after being impacted by a ball bearing according to one or more embodiments of the present disclosure; and

[0058] Figure 7 is a graph of measured optical transmittance of a number of different intermediate layers having a thickness of 0.1 mm according to one or more embodiments of the present disclosure. DETAILED DESCRIPTION

[0059] Reference will now be made in detail to embodiments of windows for infrared sensing applications such as LIDAR sensors. Wherever possible, the same reference numerals will be used throughout the accompanying drawings to refer to the same or similar parts. The window described herein includes an asymmetric lamination comprising a first glass interlayer, a second glass interlayer, and an intermediate layer connecting the first glass interlayer to the second glass interlayer. The first glass interlayer includes a first thickness and forms an exterior surface of the window facing the external environment of the sensor when the window is mounted on the housing. The second glass interlayer includes a second thickness and forms an interior surface of the window facing other components of the sensor (e.g., emitters and detectors) when the window is mounted on the housing. The first thickness is much greater than the second thickness (e.g., at least 2.0 times greater, at least 2.5 times greater, at least 3.0 times greater, at least 3.5 times greater, at least 4.0 times greater, at least 4.5 times greater, at least 5.0 times greater). In an embodiment, the first glass interlayer is strengthened (e.g., thermally, chemically, or mechanically) to a lesser extent than the second glass interlayer, so that the second glass interlayer exhibits a central tension in its central region that is greater than the central tension of the first glass interlayer. The second glass interlayer also exhibits compressive stress extending from its major surface to the central region to provide impact resistance and mechanical strength. The connection between the first glass interlayer and the second glass interlayer through the interlayer described herein can also help dissipate energy from an impact event because the interlayer layer can absorb energy from the impact and dissipate the energy and make crack propagation less likely.

[0060] The asymmetric laminated structure of the window described herein addresses various damage mechanisms associated with vehicle-mounted sensor systems. A common cause of window damage in vehicle-mounted sensor systems is damage caused by stone impact. Stone impact can cause window fractures through several mechanisms including blunt (Hertzian) contact, sharp contact, and flexure. Blunt contact produces annular / conical cracks that start from existing defects on the outer surface and then propagate throughout the thickness of the window. Sharp contact causes damage that propagates throughout the thickness of the window and then produces radial / median cracks, and the flexure of the window activates existing cracks. Bending may expand existing cracks on the window, resulting in damage. The asymmetric laminated structure of the window described herein beneficially addresses all three mechanisms that cause fractures. For example, the increased thickness of the first glass interlayer increases the distance that sharp impact damage must propagate before producing radial / median fractures, making such fractures unlikely. The relatively high strengthening of the second glass interlayer provides high flexural strength, making flexural failure unlikely. The low central tension in the first glass interlayer also helps to prevent crack propagation of cracks caused by subsurface damage by reducing the crack propagation energy stored in the glass. As a result, the asymmetric laminate structure of the windows described herein makes fracture and crack propagation caused by various cracks less likely, thereby improving the life and reliability of the on-board sensor system.

[0061] As described herein, the windows described herein exhibit greater impact resistance than certain existing monolithic glass interlayers having the same or even greater thickness. Such impact resistance makes fracture and crack propagation in the first glass interlayer or the second glass interlayer less likely. Such durability is particularly advantageous in sensor applications because radial / average cracks in either of the glass interlayers may scatter light propagating through the window (e.g., from a transmitter associated with the sensor) and negatively affect sensor performance. In addition, in certain sensors such as LiDAR sensors, the sensor assembly may be housed in a hermetically sealed sensor cavity to provide reliable performance over the service life of the sensor. The improved impact resistance of the windows described herein beneficially helps maintain the airtightness of the sensor cavity, even when the window is subjected to relatively severe impact events. As described herein, when the first glass interlayer is impacted at a 45° angle by a 1g ball bearing traveling at 160.93 km / hr, the window according to the present disclosure can maintain the airtightness of the sensor cavity. For impacts at half this speed, existing monolithic windows may not be able to maintain airtightness, even when having a thickness greater than the window described herein. Thinning can further enhance impact performance by dissipating energy through deflection.

[0062] The materials of the various components of the windows described herein may also be selected to favorably affect durability and impact resistance. For example, in an embodiment, the first glass interlayer is composed of a glass that tends to exhibit abnormal fracture behavior when in contact with a Vickers indenter, as described herein. Such a glass resists median / radial crack propagation and tends to retain damage caused by an impact event in a region near the initial impact point, thereby minimizing deleterious optical effects. In addition, the inner glass interlayer may be formed of a glass (e.g., alkali-aluminosilicate glass, alkali-aluminoborosilicate glass) that can be chemically strengthened to provide a relatively high amount of compressive stress (e.g., at least 250 MPa) at the major surface of the inner glass interlayer to achieve high surface strength and flexural strength.

[0063] The materials of each component of the asymmetric laminate structure described herein are also selected to exhibit favorable optical properties in a wavelength range of interest associated with the sensor. For example, in an embodiment, both the first glass interlayer and the second glass interlayer may be formed of a glass that exhibits a relatively high optical transmittance (e.g., an average transmittance greater than or equal to 95%) in a 50nm wavelength range of interest associated with a particular sensor application. The 50nm wavelength range of interest may be included in a wavelength range of 800nm ​​to 1800nm ​​(e.g., the 50nm wavelength range of interest may include a center wavelength ranging from 925nm to 975nm or from 1525nm to 1725nm).

[0064] The interlayer material may also be selected to have an average transmittance greater than or equal to 98% (e.g., greater than or equal to 98.25%, greater than or equal to 98.5%, greater than or equal to 98.75%, greater than or equal to 99.0%, greater than or equal to 99.25%) over the 50 nm wavelength range of interest alone (e.g., greater than or equal to 98.25%, greater than or equal to 98.5%, greater than or equal to 98.75%, greater than or equal to 99.0%, greater than or equal to 99.25%). As a result, the first glass interlayer, the second glass interlayer, and the interlayer in combination (without any additional layered films / coatings) may exhibit an average transmittance greater than 90% (e.g., greater than or equal to 90.25%, greater than or equal to 90.5%, greater than or equal to 90.75%, greater than or equal to 91.0%, greater than or equal to 91.25%) over the 50 nm wavelength range of interest. Such optical performance is superior to that which can be obtained when assembling a glass laminate using a typical polymer interlayer (such as a polyvinyl butyral interlayer). In an embodiment, the interlayer comprises a 0.05 mm to 1.5 mm thick layer of an optically clear adhesive or a UV-cured acrylate resin. Such materials provide the aforementioned optical properties while reliably joining glass sandwiches to one another.

[0065] The optical performance attributes of the windows described herein may also be enhanced by including one or more layered films on the major surfaces of the first glass interlayer and the second glass interlayer sheets. In embodiments, for example, the windows described herein may include a first layered film and a second layered film disposed on the first glass interlayer and the second glass interlayer, respectively, the first layered film and the second layered film being composed of alternating layers of a higher refractive index material and a lower refractive index material and being configured to provide relatively high transmittance and relatively low reflectivity in the 50nm wavelength range of interest. When the window is installed in a LIDAR system, the first layered film may face away from the sensor / electromagnetic radiation transmitter and be exposed to the external environment, while the second layered film may face the sensor / electromagnetic radiation transmitter. That is, when the LIDAR system is viewed from the outside, the observer may see the first layered film. Light emitted by the electromagnetic radiation transmitter may initially be incident on the second layered film before propagating through the substrate. According to the present disclosure, the first layered film of the window described herein may include one or more scratch-resistant layers of a relatively thick (e.g., greater than or equal to 500nm) high refractive index material. The scratch resistant layer can be embedded within the first layered film such that the window comprises a maximum nanoindentation hardness greater than or equal to 8 GPa (e.g., greater than or equal to 10 GPa, greater than or equal to 12 GPa, greater than or equal to 14 GPa) when measured on the first layered film by a Bosch Indenter Hardness Test. Such nanoindentation hardness beneficially provides scratch resistance and improves the performance of the LIDAR system.

[0066] In aspects, the alternating layers of the first and second layered films of the windows described herein are also constructed to provide the optical performance attributes desired for operation of the LIDAR system in the infrared spectrum. In embodiments, the number, thickness, number, and materials of the alternating layers of the first and second layered films are configured such that the window has an average percent transmittance greater than or equal to 95% calculated over a 50 nm wavelength range for light normally incident on the window. The number, thickness, number, and materials of the alternating layers of the first and second layered films may be configured such that the window also comprises an average reflectivity less than or equal to 10% over a 50 nm wavelength range of interest for light normally incident on the window.

[0067] Thus, the windows described herein, by containing an asymmetric laminate structure in combination with at least one layered film comprising a scratch-resistant layer on a first glass interlayer, can provide enhanced puncture and scratch resistance, thereby greatly improving the life and reliability of vehicle-based sensing systems while providing favorable optical performance characteristics within the desired wavelength range of interest.

[0068] Unless otherwise indicated, the total reflectivity, specular reflectivity, and average reflectivity values ​​provided herein are dual-surface reflectivity values, representing the total reflectivity of the entire window, including the reflectivity associated with various material interfaces in the window (e.g., between air and layered film, between layered film and substrate, etc.). Unless otherwise indicated, the reflectivity values ​​provided in the infrared are measured from a side of the second layered film described herein (e.g., from a side positioned facing the sensor and emitter of the LIDAR system), and the reflectivity values ​​provided in the visible light are measured from a side of the first layered film described herein (e.g., from a side positioned facing the external environment of the LIDAR system).

[0069] Unless otherwise indicated herein, average transmittance and reflectance values ​​are calculated using the percent reflectance and transmittance values ​​at various wavelengths within a specified wavelength range. Average reflectance and transmittance values ​​can be calculated by measuring the reflectance and transmittance values ​​at every five integer wavelengths (including the endpoints) within the desired wavelength range and averaging those values ​​(e.g., when calculating the average transmittance within a wavelength range of 1540nm to 1560nm, the transmittance values ​​can be measured at 1540nm, 1545nm, 1550nm, 1550nm, and 1560nm and averaged).

[0070] Unless otherwise noted herein, CIELAB color space a* and b* and lightness L* values ​​are measured / simulated using D65 illuminant.

[0071] As used herein, the term "dark appearance" or "black appearance" refers to the reflective appearance of a window when viewed from an exterior surface. A window having a dark appearance or black appearance according to the present disclosure comprises a CIELAB lightness L* value of less than 45 when viewed from an angle of 60° or less.

[0072] As used herein, the term "strengthened", when used with reference to a glass interlayer or glass layer, refers to a glass substrate that can be strengthened chemically, mechanically, thermally, or by various combinations of chemical, mechanical, and / or thermal strengthening to impart a surface compressive stress value to a compressive stress region and a maximum CT value to a central tension region. Such a strengthened glass substrate also includes a corresponding surface CS, and a compressive stress region extending from the surface to the DOC). Any one or more of the size of the surface CS, the size of the DOC, and the size of the maximum CT value can be adjusted by the strengthening process. As used herein, DOC refers to the depth at which stress changes from compression to tension. Unless otherwise indicated, CT and CS are expressed herein in megapascals (MPa), while thickness and DOC are expressed in millimeters or micrometers.

[0073] CS and DOC are measured by a surface stress meter (FSM) using a commercially available instrument such as the FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurement relies on accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. SOC is measured according to Procedure C (Glass Disc Method) described in ASTM Standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the contents of which are incorporated herein by reference in their entirety.

[0074] When compressive stress is measured using FSM, CS is related to CT by the following approximate relationship (Equation 1): CT ≈ (CS × DOC) / (thickness - 2 × DOC), where thickness is the total thickness of the strengthened glass substrate. Mechanically strengthened glass substrates may include compressive stress regions and central tension regions resulting from mismatches in thermal expansion coefficients between portions of the substrate. Chemically strengthened glass substrates may include compressive stress regions and central tension regions resulting from an ion exchange process. In chemically strengthened glass substrates, the stress profile is generated by the replacement of smaller ions with larger ions at temperatures below the temperature at which the glass network can relax. The larger volume of incoming ions generates CS on the surface portions of the substrate and tension (CT) in the center of the glass. In thermally strengthened substrates, CS regions are formed by heating the substrate to a high temperature above the glass transition temperature, close to the softening point of the glass, and then cooling the surface region of the glass faster than the interior region of the glass. The different cooling rates between the surface region and the interior region generate a residual surface CS, which in turn generates a corresponding CT in the center region of the glass.

[0075] Unless explicitly stated otherwise, any method described herein should not be construed as requiring that its steps be performed in a specific order. Therefore, in the event that a method claim does not actually recite the order in which its steps are to be followed or does not otherwise specifically state in the claims or specification that the steps are to be limited to a specific order, no order is intended to be inferred in any respect. This is true for any possible non-express basis for interpretation, including: logical matters or operational flow regarding the arrangement of steps; ordinary meaning derived from grammatical organization or punctuation; the number or type of embodiments described in the specification.

[0076] As used herein, the term "and / or" when used in a list of two or more items means that any one of the listed items may be employed alone or any combination of two or more of the listed items may be employed. For example, if a composition is described as containing components A, B, and / or C, the composition may contain A alone; B alone; C alone; A and B in combination; A and C in combination; B and C in combination; or A, B, and C in combination.

[0077] Modifications to the present disclosure will occur to those skilled in the art and to those who make or use the present disclosure. Therefore, it should be understood that the embodiments shown in the drawings and described above are for illustrative purposes only and are not intended to limit the scope of the present disclosure, which is defined by the following claims, as interpreted in accordance with patent law principles, including the doctrine of equivalents.

[0078] In this document, relational terms, such as first and second, top and bottom, etc., are used only to distinguish one entity or action from another entity or action, and do not necessarily require or imply any actual such relationship or order between such entities or actions. As used herein, the terms "comprises", "includes" or any other variation thereof are intended to cover non-exclusive inclusions, such that a process, method, object, or device comprising a series of elements does not only include those elements, but may include other elements that are not explicitly listed or inherent to such a process, method, object, or device. In the absence of further restrictions, the element after "comprises..." does not exclude the presence of additional identical elements in the process, method, object, or device comprising the element.

[0079] As used herein, the term "about" means that the amount, size, formulation, parameter and other quantities and characteristics are not and need not be exact, but may be approximate and / or larger or smaller as needed, thereby reflecting tolerances, conversion factors, truncation, measurement errors, etc., and other factors known to those skilled in the art. When the term "about" is used to describe the value or end point of a range, the disclosure should be understood to include the specific value or end point referred to. Regardless of whether the numerical value or end point of a range in this specification is described as "about", the numerical value or end point of the range is intended to include two embodiments: an embodiment modified by "about", and an embodiment not modified by "about". It should be further understood that the endpoints of each in the range are meaningful in terms of being related to another endpoint and being independent of another endpoint.

[0080] The term "formed from" may mean one or more of comprising, consisting essentially of, or consisting of. For example, a component formed from a particular material may comprise, consist essentially of, or consist of the particular material.

[0081] The term "disposed" is used herein to refer to a layer or sublayer being coated, deposited, formed or otherwise disposed on a surface. The term disposed may include a layer / sublayer being disposed in direct contact with an adjacent layer / sublayer or separated by an intervening material that may or may not form a layer.

[0082] Reference now Figure 1 , the vehicle 10 includes one or more LIDAR systems 12. The one or more LIDAR systems 12 may be positioned anywhere on or within the vehicle 10. For example, the one or more LIDAR systems 12 may be positioned on a roof 14 of the vehicle 10 and / or on a front portion 16 of the vehicle 10.

[0083] Reference now Figure 2, each of the one or more LIDAR systems 12 includes an electromagnetic radiation emitter and a sensor 18, which may be enclosed in a housing 20 as is known in the art. The housing 20 may be a shell formed of a suitable material (e.g., a metal or polymer-based material) that protects the radiation emitter and sensor 18 from an external environment 26. The LIDAR system 12 further includes a window 24 attached to the housing 20 to form a sensor cavity 15. In an embodiment, the window 24 is attached to the housing 20 so that the sensor cavity 15 is hermetically sealed to prevent particles or other debris from the external environment from entering the sensor cavity 15 and degrading the performance of the LIDAR system 12. The window 24 may be coupled to the housing 20 using any suitable connection method. In an embodiment, the window 24 is attached to the front surface (e.g., of the sidewall) of the housing 20 using a suitable adhesive. In an embodiment, the window 24 is attached to the housing 20 by one or more fasteners extending through at least one glass layer (e.g., an unstrengthened first glass interlayer, as described herein). In embodiments, one or more layers of the asymmetric lamination described herein may have different dimensions to facilitate attaching the window 24 to the housing 20. For example, the first outer layer of glass interlayer may have dimensions that are smaller than the dimensions of the second inner layer of glass interlayer, and the window 24 may be panel mounted in the housing 20 such that the outer surface of the window 24 is mounted flush with the front surface of the housing. Any suitable connection method may be used.

[0084] In an embodiment, the electromagnetic radiation emitter and sensor 18 emits emitted radiation 22 having a certain wavelength or wavelength range (e.g., within a 50 nm wavelength range of interest contained in a wavelength range of 800 nm to 1800 nm). The emitted radiation 22 leaves the housing 20 through a window 24, which is in the path of the emitted electromagnetic radiation. If an object (not illustrated) in the external environment 26 is in the path of the emitted radiation 22, the emitted radiation 22 will be reflected from the object and returned to the electromagnetic radiation emitter and sensor 18 as reflected radiation 28. The reflected radiation 28 passes through the window 24 again to the electromagnetic radiation emitter and sensor 18. In an embodiment, the emitted radiation 22 and the reflected radiation 28 may include light within a suitable wavelength range of interest from 800 nm to 1800 nm. For example, the emitted radiation 22 and the reflected radiation 28 may be within a suitable 50 nm wavelength range. The 50 nm wavelength range may have a central wavelength (e.g., a wavelength of maximum intensity of the emitted radiation 22) that may vary depending on the application. In some embodiments, the central wavelength may be greater than or equal to 925 nm and less than or equal to 975 nm, greater than or equal to 1525 nm and less than or equal to 1575 nm. In embodiments, for , the emitted radiation 22 and the reflected radiation 28 may be greater than or equal to 1400 nm and less than or equal to 1600 nm (e.g., greater than or equal to 1500 nm and less than or equal to 1600 nm, greater than or equal to 1525 nm and less than or equal to 1575 nm, about 1550 nm, and 1550 nm). Electromagnetic radiation other than the reflected radiation 28, such as electromagnetic radiation having wavelengths in the visible spectrum, part of the ultraviolet range, may also interact with the window 24. As described herein, the window 24 may be designed to provide desired performance attributes in such wavelength ranges by incorporating one or more layered films.

[0085] As used herein, the "visible spectrum" is the portion of the electromagnetic spectrum visible to the human eye, and generally refers to electromagnetic radiation with wavelengths ranging from about 380 nm or 400 nm to about 700 nm. The "ultraviolet range" is the portion of the electromagnetic spectrum with wavelengths between about 10 nm and about 400 nm. The "infrared range" of the electromagnetic spectrum begins at about 700 nm and extends to longer wavelengths. The sun produces solar electromagnetic radiation, commonly referred to as "sunlight," with wavelengths falling within all three ranges.

[0086] Reference now Figure 3A, the window 24 of each of the one or more LIDAR systems 12 includes a substrate 30. The substrate 30 includes a first surface 32 and a second surface 34. The first surface 32 and the second surface 34 are major surfaces of the substrate 30. The first surface 32 is closest to the external environment 26. The second surface 34 is closest to the electromagnetic radiation emitter and sensor 18. The emitted radiation 22 encounters the second surface 34 and then the first surface 32. The reflected radiation 28 encounters the first surface 32 and then the second surface 34. The substrate 30 further includes a first layered film 36 disposed on the first surface 32 of the substrate 30 and (optionally) a second layered film 38 disposed on the second surface 34 of the substrate 30. Examples are described herein in which the window 24 includes both the first layered film 36 and the second layered film 38. Embodiments in which the window 24 includes only one layered film (e.g., only the first layered film 36 or the second layered film 38) are also contemplated. It should be understood that the window 24 as described herein is not limited to vehicle applications, and may be used in any application where the window 24 will help provide improved impact and optical properties, as further described herein.

[0087] Reference now Figure 3B , showing the components of the substrate 30 in more detail. As shown, the substrate 30 includes an asymmetric laminate structure 300, which includes a first glass interlayer 200 having a first thickness 205, a second glass interlayer 320 having a second thickness 325, and an intermediate layer 330 that connects the first glass interlayer 200 to the second glass interlayer 320 and includes a third thickness 335. The first glass interlayer 200 includes a first major surface 202 and a second major surface 204. The thickness 205 extends between the first major surface 202 and the second major surface 204 in a direction perpendicular to the first major surface 202. The first major surface 202 forms the first surface 32 of the substrate 30 (for example, such that the first major surface 202 faces the Figure 2 The second glass interlayer 320 includes a third major surface 332 and a fourth major surface 334. The second thickness 325 extends between the third major surface 332 and the fourth major surface 334 in a direction perpendicular to the third major surface 332. The fourth major surface 334 forms the second surface 34 of the substrate 30 (for example, such that the fourth major surface 334 faces the Figure 2 Sensor cavity 215 depicted in FIG.

[0088] In an embodiment, the first thickness 205 is significantly greater than the second thickness 325. For example, in an embodiment, the first thickness 205 is at least 2.0 times greater than the second thickness (e.g., at least 2.5 times greater, at least 3.0 times greater, at least 3.5 times greater, at least 4.0 times greater, at least 4.5 times greater, at least 5.0 times greater). In an embodiment, the ratio between the first thickness 205 and the second thickness 325 (first thickness / second thickness) can be greater than 2: 1, such as in the range of 2: 1 to 20: 1, 3: 1 to 20: 1, 3: 1 to 15: 1, 3: 1 to 10: 1, 4: 1 to 20: 1, 4: 1 to 15: 1, 4: 1 to 10: 1, 4.5: 1 to 20: 1, 4.5: 1 to 15: 1, 4.5: 1 to 10: 1, 5: 1 to 20: 1, 5: 1 to 15: 1, 5: 1 to 10: 1, 5.75: 1 to 20: 1, 5.75: 1 to 15: 1, or 5.75: 1 to 10: 1. As described herein, such an asymmetric structure 300 beneficially enhances the impact performance of the window 24.

[0089] In an embodiment, the first thickness 205 is at least 0.5 mm, at least 1 mm, at least 2 mm, at least 3 mm, at least 3.3 mm, or at least 3.8 mm. In one or more embodiments, the first thickness ranges from about 1.5 mm to about 8 mm, 1.6 mm to about 8 mm, from about 1.8 mm to about 8 mm, from about 2 mm to about 8 mm, from about 2.2 mm to about 8 mm, from about 2.4 mm to about 8 mm, from about 2.6 mm to about 8 mm, from about 2.8 mm to about 8 mm, from about 3 mm to about 8 mm, from about 3.1 mm to about 8 mm, from about 3.2 mm to about 8 mm, from about 3.3 mm to about 8 mm, from about 3.4 mm to about 8 mm, from about 3.5 mm to about 8 mm, from about 3.6 mm to about 8mm, from about 3.7mm to about 8mm, from about 3.8mm to about 8mm, from about 3.9mm to about 8mm, from about 4mm to about 8mm, from about 4.2mm to about 8mm, from about 4.4mm to about 8mm, from about 4.5mm to about 8mm, from about 4.6mm to about 8mm, from about 4.8mm to about 8mm, from about 5mm to about 8mm, from about 5.2mm to about 8mm, from about 5.4mm to about 8mm, from about 5.5mm to about 8mm, from about 5.6mm to about 8mm, from about 5.8mm to about 8mm, from about 1.6mm to about 5 .8mm, from about 1.6mm to about 5.6mm, from about 1.6mm to about 5.5mm, from about 1.6mm to about 5.4mm, from about 1.6mm to about 5.2mm, from about 1.6mm to about 5mm, from about 1.6mm to about 4.8mm, from about 1.6mm to about 4.6mm, from about 1.6mm to about 4.4mm, from about 1.6mm to about 4.2mm, from about 1.6mm to about 4mm, from about 1.6mm to about 3.9mm, from about 1.6mm to about 3.8mm, from about 1.6mm to about 3.7mm, from about 1.6mm to about From about 1.6 mm to about 3.5 mm, from about 1.6 mm to about 3.4 mm, from about 1.6 mm to about 3.3 mm, from about 1.6 mm to about 3.2 mm, from about 1.6 mm to about 3.1 mm, from about 1.6 mm to about 3 mm, from about 1.6 mm to about 2.8 mm, from about 1.6 mm to about 2.6 mm, from about 1.6 mm to about 2.4 mm, from about 1.6 mm to about 2.2 mm, from about 1.6 mm to about 2 mm, from about 1.6 mm to about 1.8 mm, from about 3 mm to about 5 mm, or from about 3 mm to about 4 mm.

[0090] In one or more embodiments, the second thickness 325 may be in the range of about 0.05 mm to about 1.5 mm, for example, in the range of about 0.05 mm to about 1.2 mm, about 0.05 mm to about 1.1 mm, about 0.05 mm to about 1.0 mm, about 0.05 mm to about 0.9 mm, in the range of about 0.05 mm to about 0.8 mm, in the range of about 0.05 mm to about 0.7 mm, in the range of about 0.05 mm to about 0.6 mm, in the range of about 0.05 mm to about 0.5 mm, in the range of about 0.05 mm to about 0.4 mm, in the range of about 0.05 mm to about 0.3 mm, in the range of about 0.05 mm to about 0.2 mm, or in the range of about 0.05 mm to about 0.15 mm.

[0091] The thickness values ​​described herein are maximum thicknesses. In one or more embodiments, the first glass interlayer 200 and the second glass interlayer 320 have substantially uniform thicknesses. In embodiments, the first thickness 205 and the second thickness 305 may vary depending on the spatial position. Although the depicted embodiments are flat, embodiments are also contemplated in which one or more of the first glass interlayer 200 and the second glass interlayer 320 are curved by suitable techniques (e.g., hot forming or cold forming).

[0092] In an embodiment, the first glass interlayer 200 is strengthened to a lesser extent than the second glass interlayer 320, so that the first glass interlayer 200 and the second glass interlayer 320 contain different stress distributions therein (e.g., except for the external force applied to the substrate 30). The first glass interlayer 200 generally has a central tension in its central region that is less than the central tension of the second glass interlayer 320. In an embodiment, for example, the second glass interlayer 320 is strengthened and the first glass interlayer 200 is not strengthened (but may be annealed as appropriate), so that the first glass interlayer exhibits a surface compressive stress of less than about 10 MPa, less than about 3 MPa, or about 2.5 MPa or less, 2 MPa or less, 1.5 MPa or less, 1 MPa or less, or about 0.5 MPa or less. In such an embodiment, the second glass interlayer 320 may be thermally strengthened, mechanically strengthened, or chemically strengthened. In an embodiment, for example, the second glass interlayer 320 is chemically strengthened such that at the third major surface 332 and the fourth major surface 334, the second glass interlayer 320 comprises a surface compressive stress of at least 250 MPa, at least 300 MPa, or at least 400 MPa, or at least 500 MPa, or at least 600 MPa, or at least 700 MPa, at least 800 MPa, at least 900 MPa, or at least 1000 MPa. In various embodiments, the second glass interlayer 320 may include a surface compressive stress magnitude in the range of about 250 MPa to about 1100 MPa, about 250 MPa to about 900 MPa, about 300 MPa to about 900 MPa, about 400 MPa to about 900 MPa, or in the range of about 500 MPa to about 900 MPa, or in the range of about 600 MPa to about 900 MPa, or in the range of about 700 MPa to about 900 MPa, or in the range of about 800 MPa to about 900 MPa at one or more of the third major surface 332 and the fourth major surface 334.

[0093] In an embodiment, the second glass interlayer 320 may include at least one compressive stress region extending from one or more of the third major surface 332 and the fourth major surface 334 to a depth of compression (DOC). In an embodiment, the DOC is 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, or 50 μm or more. In an embodiment, the DOC is in a range of about 30 μm to about 150 μm, about 30 μm to about 90 μm, or in a range of about 40 μm to about 80 μm, or in a range of about 40 μm to about 70 μm, or in a range of about 40 μm to about 60 μm, or in a range of about 40 μm to about 50 μm.

[0094] The materials of the first glass interlayer 200 and the second glass interlayer 320 may vary. According to one or more embodiments, the materials used for the first glass interlayer 200 and the second glass interlayer 320 may be the same material (except for the difference caused by the strengthening treatment) or different materials. In an exemplary embodiment, one or both of the first glass interlayer 200 and the second glass interlayer 320 may be glass (e.g., soda-lime glass, alkali-containing aluminosilicate glass, alkali-containing borosilicate glass, and / or alkali-containing aluminoborosilicate glass) or glass ceramics (including Li2O-Al2O3-SiO2 system (i.e., LAS system) glass ceramics, MgO-Al2O3-SiO2 system (i.e., MAS system) glass ceramics, glass ceramics including any one or more of mullite, spinel, α quartz, β quartz solid solution, petalite, lithium disilicate, β spodumene, nepheline, and alumina in a crystalline stage).

[0095] The first glass interlayer 200 and the second glass interlayer 320 can be provided using a variety of different processes. Exemplary glass substrate forming methods include float glass processes and down-draw processes such as fusion drawing and slot drawing. Glass substrates prepared by the float glass process can be characterized by a smooth surface and uniform thickness by floating molten glass on a bed of molten metal (usually tin). In an exemplary process, the molten glass fed to the surface of the molten tin bed forms a float glass ribbon. As the glass ribbon flows along the tin bath, the temperature gradually decreases until the glass ribbon solidifies into a solid glass substrate that can be lifted from the tin onto a roller. Once the glass substrate leaves the bath, it can be further cooled and annealed to reduce internal stress.

[0096] The down-draw process produces a glass substrate with a relatively pristine surface having a uniform thickness. Since the average flexural strength of the glass substrate is controlled by the amount and size of the surface cracks, the pristine surface with minimal contact has a higher initial strength. When this high-strength glass substrate is further strengthened (e.g., chemically), the resulting strength can be higher than that of a glass substrate whose surface has been ground and polished. The down-drawn glass substrate can be drawn to a thickness of less than about 2 mm. In addition, the down-drawn glass substrate has a very flat, smooth surface that can be used in the final application without expensive grinding and polishing.

[0097] For example, the fusion drawing process uses a drawing tank having a channel for receiving molten glass raw materials. The channel has a weir opening at the top along the length of the channel on both sides of the channel. When the channel is filled with molten material, the molten glass overflows the weir. Due to gravity, the molten glass flows downward along the outer surface of the drawing trough as two flowing glass films. These outer surfaces of the drawing trough extend downward and inward so that they are connected at the edge below the drawing trough. The two flowing glass films are connected at this edge to fuse and form a single flowing glass substrate. The fusion drawing method provides the following advantages: since the two glass films flowing on the channel are fused together, the outer surface of the resulting glass substrate does not contact any part of the equipment. Therefore, the surface properties of the fusion drawn glass substrate are not affected by such contact.

[0098] The slot draw process is different from the fusion draw method. In the slot draw process, molten raw material glass is provided to a drawing tank. The bottom of the drawing tank has an open slot with a nozzle extending along the length of the tank. The molten glass flows through the slot / nozzle and is sucked down as a continuous substrate and into the annealing zone.

[0099] Once formed, the glass substrate can be strengthened to form a strengthened glass substrate as described herein. It should be noted that a glass ceramic substrate can also be strengthened in the same manner as a glass substrate.

[0100] Examples of glass that can be used for the first glass interlayer 200 or the second glass interlayer 320 described herein may include borosilicate glass compositions, alkali-containing aluminosilicate glass compositions, alkali-containing aluminoborosilicate glass compositions, soda-lime silicate glass compositions, and other suitable glass compositions. Certain glass compositions may be characterized by being ion-exchangeable. As used herein, "ion-exchangeable" means that a substrate comprising the composition is capable of exchanging cations located at or near the surface of the substrate with cations of the same valence state that are larger or smaller in size. An exemplary glass composition comprises SiO2, B2O3, and Na2O, wherein (SiO2+B2O3)≥66 mol%, and Na2O≥9 mol%. In some embodiments, a suitable glass composition further comprises at least one of K2O, MgO, and CaO. In a specific embodiment, the glass composition used in the substrate may include: 61 mol% to 75 mol% SiO2; 7 mol% to 15 mol% Al2O3; 0 mol% to 12 mol% B2O3; 9 mol% to 21 mol% Na2O; 0 mol% to 4 mol% K2O; 0 mol% to 7 mol% MgO; and 0 mol% to 3 mol% CaO.

[0101] Another exemplary glass composition suitable for the first glass interlayer 200 and the second glass interlayer 320 includes: 60 mol% to 70 mol% SiO2; 6 mol% to 14 mol% Al2O3; 0 mol% to 15 mol% B2O3; 0 mol% to 15 mol% Li2O; 0 mol% to 20 mol% Na2O; 0 mol% to 10 mol% K2O; 0 mol% to 8 mol% MgO; 0 mol% to 10 mol% CaO; 0 mol% to 5 mol% ZrO2; 0 mol% to 1 mol% SnO2; 0 mol% to 1 mol% CeO2; less than 50 ppm As2O3; and less than 50 ppm Sb2O3; wherein 12 mol%≤(Li2O+Na2O+K2)≤20 mol%, and 0 mol%≤(MgO+CaO)≤10 mol%.

[0102] Another exemplary glass composition suitable for the first glass interlayer 200 and the second glass interlayer 320 includes: 63.5 mol% to 66.5 mol% SiO2; 8 mol% to 12 mol% Al2O3; 0 mol% to 3 mol% B2O3; 0 mol% to 5 mol% Li2O; 8 mol% to 18 mol% Na2O; 0 mol% to 5 mol% K2O; 1 mol% to 7 mol% MgO; 0 mol% to 2.5 mol% CaO; 0 mol% to 3 mol% ZrO2; 0.05 mol% to 0.25 mol% SnO2; 0.05 mol% to 0.5 mol% CeO2; less than 50 ppm As2O3; and less than 50 ppm Sb2O3; wherein 14 mol%≤(Li2O+Na2O+K2O)≤18 mol%, and 2 mol%≤(MgO+CaO)≤7 mol%.

[0103] In a specific embodiment, the alkali-aluminosilicate glass composition suitable for the first glass interlayer 200 and the second glass interlayer 320 includes: aluminum oxide, at least one alkali metal, and in some embodiments, greater than 50 mol% SiO2, in other embodiments, at least 58 mol% SiO2, and in still other embodiments, at least 60 mol% SiO2, wherein the ratio ((Al2O3+B2O3) / ∑ modifier)>1, wherein in the ratio, the components are expressed in mol% and the modifier is an alkali metal oxide. In a specific embodiment, the glass composition includes: 58 mol% to 72 mol% SiO2; 9 mol% to 17 mol% Al2O3; 2 mol% to 12 mol% B2O3; 8 mol% to 16 mol% Na2O; and 0 mol% to 4 mol% K2O, wherein the ratio ((Al2O3+B2O3) / ∑ modifier)>1.

[0104] In yet another embodiment, the first glass interlayer 200 and the second glass interlayer plate 320 may include an alkali-aluminosilicate glass composition, wherein the alkali-aluminosilicate glass composition includes: 64 mol% to 68 mol% SiO2; 12 mol% to 16 mol% Na2O; 8 mol% to 12 mol% Al2O3; 0 mol% to 3 mol% B2O3; 2 mol% to 5 mol% K2O; 4 mol% to 6 mol% MgO; and 0 mol% to 5 mol% % CaO, of which 66 mol % ≤ SiO2+B2O3+CaO ≤ 69 mol %; Na2O+K2O+B2O3+MgO+CaO+SrO>10 mol %; 5 mol % ≤ MgO+CaO+SrO ≤ 8 mol %; (Na2O+B2O3)-Al2O3 ≤ 2 mol %; 2 mol % ≤ Na2O-Al2O3 ≤ 6 mol %; and 4 mol % ≤ (Na2O+K2O)-Al2O3 ≤ 10 mol %.

[0105] In an alternative embodiment, the first glass interlayer 200 and the second glass interlayer 320 may include an alkali-aluminosilicate glass composition comprising: 2 mol % or more of Al2O3 and / or ZrO2; or 4 mol % or more of Al2O3 and / or ZrO2.

[0106] In an embodiment, the first glass interlayer 200 is formed of an abnormal glass composition. Abnormal glass is a glass that tends to exhibit a crack loop or densification fracture behavior in which an annular crack surrounds the initial indentation site when the glass is subjected to a Vickers indenter test, which is described in Gross et al., Crack-resistant glass with high shear band density, Journal of Non-Crystalline Solids, 494 (2018) 13-20; and Gross, Deformation and cracking behavior of glasses indented with diamond tips of various sharpness, Journal of Non-Crystalline Solids, 358 (2012) 3445-3452, both documents are incorporated as a whole. Examples of abnormal glass may be borosilicate glass (such as the glass described in PCT patent application No. PCT / US2021 / 61966 filed on December 6, 2021), certain unstrengthened aluminosilicate glasses, or glasses with relatively high silica content. Such glasses tend to exhibit impact performance characteristics superior to glasses exhibiting normal fracture behavior, in which cracks extending radially from the indentation site tend to extend through the thickness of the glass, potentially resulting in catastrophic failure. Abnormal glasses such as borosilicates may also tend to exhibit relatively low CTEs, thereby limiting thermally induced damage due to environmental exposure.

[0107] In an embodiment, the first glass interlayer 200 includes a borosilicate glass composition, and the borosilicate glass composition includes: from 60 mol% to 90 mol% SiO2; from about 1 mol% to about 20 mol% Al2O3; from 7 mol% to 16 mol% B2O3; from 2 mol% to 20 mol% R2O, wherein R2O includes a combined amount of Na2O, Li2O, and K2O. For example, in an embodiment, the borosilicate glass composition includes about 83.60 mol% SiO2, about 1.20 mol% Al2O3, about 11.60 mol% B2O3, about 3.00 mol% Na2O, and about 0.70 mol% K2O, and includes about 32×10 -7 K -1 Such borosilicate glasses may advantageously have greater thermal shock resistance than soda-lime silicate glasses currently used in certain windows, and be more resistant to crack formation from impact events from road debris (e.g., rocks or the like). Borosilicate glasses are known to exhibit abnormal cracking behavior and are less susceptible to forming cracks that propagate radially from the point of debris impact, which is particularly beneficial for automotive glass durability.

[0108] In an embodiment, the first glass interlayer 200 particularly advantageously includes a fusion-formable borosilicate glass composition described in the following patents: U.S. Provisional Patent Application No. 63 / 123,863, entitled “Fusion Formable Borosilicate Glass Composition and Articles Formed Therefrom,” filed on December 10, 2020, U.S. Provisional Patent Application No. 63 / 183,271, entitled “Fusion Formable Borosilicate Glass Composition and Articles Formed Therefrom,” filed on May 3, 2021, U.S. Provisional Patent Application No. 63 / 183,292, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield,” filed on May 3, 2021, U.S. Patent Application No. 17 / 363,266, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield,” filed on June 30, 2021, and U.S. Patent Application No. 17 / 363,267, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield,” filed on December 6, 2021. The present invention relates to an embodiment of the present invention and an embodiment of the present invention, wherein the borosilicate glass composition comprises SiO2, B2O3, Al2O3, one or more alkali metal oxides and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO and ZnO. In an embodiment, the borosilicate glass composition includes, for example, greater than or equal to 11 mol % and less than or equal to 16 mol % B2O3, greater than or equal to 2 mol % and less than or equal to 6 mol % Al2O3, and greater than or equal to 7.0 mol % of the total amount of Na2O, K2O, MgO, and CaO.The molar percentage concentrations on an oxide basis of SiO2, B2O3, one or more alkali metal oxides, Al2O3 and one or more alkaline earth metal oxides satisfy the following relationships: (R2O+R'O)≥Al and 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, where R2O is the sum of the concentrations of the one or more alkali metal oxides and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides. Such glasses have been found to exhibit good annular cracking behavior, thereby preventing cracks from propagating radially from the point of impact.

[0109] In an embodiment, the first glass interlayer 200 includes a fusion-formable borosilicate glass composition, the fusion-formable borosilicate glass composition includes 74 mol% to 80 mol% SiO2, 2.5 mol% to 6 mol% Al2O3, 11.5 mol% to 18 mol% B2O3, 4.5 mol% to 8 mol% Na2O, 0.5 mol% to 3 mol% K2O, 0.5 mol% to 2.5 mol% MgO, and 0 mol% to 4 mol% CaO (e.g., such that the combined amount of CaO and MgO is less than 5 mol%), and includes greater than or equal to 32.5×10 -7 K -1 and less than or equal to 56×10 -7 K -1 (For example, greater than or equal to 40×10 -7 K -1 and less than or equal to 50x10 -7 K -1 , greater than or equal to 42×10 -7 K -1 and less than or equal to 48×10 -7 K -1 , greater than or equal to 43×10 -7 K -1 and less than or equal to 47×10 -7 K -1) CTE. Such a fusion-formable borosilicate glass composition may include molar percentage concentrations of SiO2, B2O3, one or more alkali metal oxides (R2O), Al2O3, and one or more divalent cation oxides, based on oxides, such that the concentrations satisfy some (e.g., one or more combinations) or all of the following relationships: (Relationship 1) SiO2 ≥ 72 mol % (such as SiO2 ≥ 72.0, such as SiO2 ≥ 73.0, such as SiO2 ≥ 74.0), and / or SiO2 ≤ 92 (such as SiO2 ≤ 90); (Relationship 2) B2O3 ≥ 10 mol % (such as B2O3 ≥ 10.0, such as B2O3≥10.5), and / or B2O3≤20 (such as B2O3≤18); (Relation 3) (R2O+R'O)≥Al2O3, such as (R2O+R'O)≥(Al2O3+1), such as (R2O+R'O)≥(Al2O3+2); and / or (Relation 4) 0.80≤(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])≤0.93, wherein R2O is the sum of the concentrations of one or more alkali metal oxides, and when included in the borosilicate glass composition, R'O is the sum of the concentrations of one or more divalent cation oxides. R2O may be, for example, the sum of Li2O, Na2O, K2O, Rb2O, Cs2O, and R'O may be, for example, the sum of MgO, CaO, SrO, BaO, and ZnO. Compositions that satisfy relations 1-4 described in this paragraph may tend to exhibit unique fracture behavior in which annular cracks are formed around the contact area between the glass and the impactor and radial crack propagation is prevented. Such fusion-formed glasses may also exhibit excellent chemical durability, scratch resistance, mechanical strength, and optical properties (e.g., from the perspective of both optical transmission and optical distortion) compared to other borosilicate glasses. Examples of such glass compositions are provided herein.

[0110] Various exemplary compositions of the borosilicate glass included in the first glass interlayer 200 will now be described. Examples 1-6 are described in Table 1 below with respect to composition and various properties.

[0111] Table 1

[0112] Examples 1 2 3 4 5 6 <![CDATA[SiO2]]> 75.35 76.72 76.14 75.18 77.19 76.36 <![CDATA[Al2O3]]> 3.54 3.54 3.54 4.07 4.04 4.07 <![CDATA[B2O3]]> 12.21 10.75 11.31 12.01 9.84 10.86 <![CDATA[Na2O]]> 4.60 4.67 4.68 4.61 4.70 4.57 <![CDATA[K2O]]> 2.13 2.18 2.18 2.93 3.05 2.94 MgO 0.99 0.99 0.99 0.02 0.02 0.02 CaO 1.03 1.02 1.02 1.05 1.03 1.03 <![CDATA[SnO2]]> 0.14 0.13 0.13 0.13 0.13 0.14 <![CDATA[Density (g / cm 3 )]]> 2.307 2.308 2.308 2.316 2.335 2.324 Strain point(℃) 512.6 518.6 516.7 515.2 528.0 520.7 LTCTE(ppm / ℃) 5.1 5.24 5.1 5.58 5.55 5.56 HTCTE(ppm / ℃) 25.44 25.26 24.79 24.52 24.6 24.58 Young's modulus(GPa) 66.6 67.7 67.1 66.7 69.2 67.7 Poisson's ratio 0.198 0.194 0.196 0.200 0.194 0.197 Fulchers A -1.531 -1.342 -1.536 -1.163 -1.159 -1.152 Fulchers B 5661.3 5468.2 5817.5 4739.4 4858.6 4848.7 <![CDATA[Fulchers T0]]> 140.9 182.3 142.8 227.7 232.4 224.8 200P temperature (℃) 1618 1683 1659 1596 1637 1629 35kP Temperature (℃) 1073 1111 1100 1058 1084 1076 200kP Temperature(℃) 970 1005 994 961 985 976 Liquid viscosity (kP) 947 672 1578 3779 2892 4013

[0113] Additional exemplary borosilicate glass compositions are described in Table 2 below.

[0114] Table 2

[0115] Examples 7 8 9 12 13 14 <![CDATA[SiO2]]> 76.75 75.93 76.38 76.34 76.06 76.15 <![CDATA[Al2O3]]> 3.57 3.53 3.56 3.56 3.54 3.54 <![CDATA[B2O3]]> 11.18 11.61 12.26 11.80 12.43 12.89 <![CDATA[Na2O]]> 6.35 4.59 4.87 4.29 4.15 3.85 <![CDATA[K2O]]> 2.04 2.13 1.01 1.96 1.95 1.80 MgO 0.00 0.03 1.81 0.95 0.86 0.82 CaO 0.01 2.05 0 0.99 0.90 0.86 <![CDATA[SnO2]]> 0.11 0.11 0.11 0.10 0.10 0.10 <![CDATA[Density (g / cm 3 )]]> 2.328 2.32 2.273 2.298 2.285 2.271 Strain point(℃) 518.6 525.8 506.2 512.7 511.1 506.6 Annealing point(℃) 564 571.4 552.9 558.7 558.2 554.9 LTCTE(ppm / ℃) 5.6 5.15 4.58 4.8 4.6 4.5 Young's modulus(GPa) 68.7 68.3 63.1 65.9 64.6 63.0 Poisson's ratio 0.192 0.192 0.196 0.196 0.2 0.2 Fulchers A -1.121 -0.974 -1.682 -1.504 -1.647 -1.835 Fulchers B 4505.1 4545.6 6535.2 12 13 14 <![CDATA[Fulchers T0]]> 255.8 251.8 69 76.34 76.06 76.15 200P temperature (℃) 1572 1640 1710 1676 1695 1718 35kP Temperature (℃) 1051 1076 1119 1097 1113 1121 200kP Temperature(℃) 957 976 1005 987 1002 1005 Liquid viscosity (kP) 582 855 1365 1021 1197 1752

[0116] As shown in Table 2, Examples 12-14 show that increasing amounts of B2O3 can have a density-reducing effect. The above examples include at least 5.5 mol% Na2O+K2O and at least 7.0 mol% Na2O+K2O+MgO+CaO in total. Based on Examples 1-2 in the table, it is believed that embodiments of the present disclosure will exhibit T 200P and liquidus viscosity, wherein the total amount of Na2O+K2O+MgO+CaO is at least 7.0 mol%, especially in the presence of at least 5.5 mol% Na2O+K2O and at least 1.5 mol% MgO+CaO. It is further believed that embodiments of the present disclosure will exhibit the necessary T for fusion forming. 200P and liquidus viscosity, wherein Na2O+K2O is at least 8 mol %, regardless of the amount of MgO and CaO.

[0117] Still reference Figure 3B , the intermediate layer 330 is formed of a suitable material, and the third thickness 335 is selected so that the substrate 30 exhibits desired optical performance attributes (e.g., in terms of reflectivity and transmittance) within a suitable wavelength range of interest. In an embodiment, for light normally incident on the intermediate layer 330, the intermediate layer 330 alone exhibits an average transmittance greater than or equal to 98% (e.g., greater than or equal to 98.25%, greater than or equal to 98.5%, greater than or equal to 98.75%, greater than or equal to 99.0%, greater than or equal to 99.25%) within the 50nm wavelength range of interest. Therefore, for light normally incident on the first surface 32, the substrate 30 in combination (without any additional layered film / coating) can exhibit an average transmittance greater than 90% (e.g., greater than or equal to 90.25%, greater than or equal to 90.5%, greater than or equal to 90.75%, greater than or equal to 91.0%, greater than or equal to 91.25%) within the 50nm wavelength range of interest. Such optical performance is superior to that which can be obtained when assembling glass laminates using typical polymer interlayers, such as polyvinyl butyral interlayers.

[0118] In an embodiment, the intermediate layer 330 is formed from a suitable optically clear adhesive (e.g., a tape-based optically clear adhesive such as 3M TM Optically Clear Adhesive 8146-1 or 3M TM In an embodiment, the intermediate layer 330 is formed of a suitable acrylate-based radiation curable resin (such as AA 3491 or S single component acrylic resin). As described with respect to the examples herein, it has been found that such materials exhibit optical performance characteristics that are favorable for various sensor wavelength ranges of interest (e.g., from 925nm to 975nm or from 1525nm to 1575nm). Any suitable interlayer material that can meet the optical and impact performance criteria described herein can be used. The method of assembling substrate 30 can vary depending on the type of adhesive used.

[0119] In an embodiment, the third thickness 335 is from 0.05 mm to 1.5, from 0.05 mm to 1.4 mm, from 0.1 to 1.4 mm, from 0.1 mm to 1.3 mm, from 0.1 mm to 1.2 mm, from 0.1 mm to 1.1 mm, from 0.1 mm to 1.0 mm, from 0.1 mm to 0.95 mm, from 0.1 mm to 0.90 mm, from 0.1 mm to 0.85 mm, from 0.1 mm to 0.80 mm, from 0.1 mm From 0.1mm to 0.75mm, from 0.1mm to 0.70mm, from 0.1mm to 0.65mm, from 0.1mm to 0.60mm, from 0.1mm to 0.55mm, from 0.1mm to 0.50mm, from 0.1mm to 0.45mm, from 0.1mm to 0.40mm, from 0.1mm to 0.35mm, from 0.1mm to 0.30mm, from 0.1mm to 0.25mm, from 0.1mm to 0.20mm. The thickness can be selected to achieve specific optical properties, depending on the selected interlayer material.

[0120] The optical properties of substrate 30 can be adjusted by incorporating different functional layers (e.g., anti-reflective coatings, decorative coatings) or surface treatments (e.g., anti-glare surface treatments). In an embodiment, for example, substrate 30 includes a layer of visible light absorbing, infrared transmissive material. Examples of such materials include infrared transmissive, visible light absorbing acrylic sheets, such as those available from ePlastics under the trade name IR acrylic 3143 and CYRO's The sheets were purchased from IR acrylic1146. IR acrylic 3143 has a transmittance of about 0% (at least less than 10%, or less than 1%) for electromagnetic radiation having a wavelength of about 700 nm or less, but has a transmittance of about 90% (greater than 85%) for wavelengths in the range of 800 nm to about 1100 nm (including 905 nm).

[0121] In embodiments, each of the layers of substrate 30 exhibits a refractive index in the range of about 1.40 to about 1.60 (e.g., at the center wavelength of the 50 nm wavelength range of interest described herein). In embodiments, the substrate exhibits an average transmittance greater than or equal to 95% (e.g., greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, greater than or equal to 99%, greater than or equal to 99.5%) throughout the 50 nm wavelength range of interest described herein.

[0122] Reference now Figure 4 and Figure 5 , the first layered film 36 and the second layered film 38 each include a number of alternating layers of one or more higher refractive index materials 40 and one or more lower refractive index materials 42. Although each of the one or more higher refractive index materials 40 and the one or more lower refractive index materials 42 are identified using the same reference numerals, it should be understood that the use of the same reference numerals does not indicate that each of the layers is composed of the same material or includes the same structure. In each of the first layered film 36 and the second layered film 38, different layers of the layers of the respective higher refractive index materials 40 and lower refractive index materials 42 may include different compositional or structural characteristics.

[0123] As used herein, the terms "higher refractive index" and "lower refractive index" refer to refractive index values ​​relative to each other, wherein one or more refractive indices of one or more higher refractive index materials 40 are greater than one or more refractive indices of one or more lower refractive index materials 42. In an embodiment, one or more higher refractive index materials 40 have a refractive index from about 1.7 to about 4.0. In an embodiment, one or more lower refractive index materials 42 have a refractive index from about 1.3 to about 1.6. In an embodiment, one or more lower refractive index materials 42 have a refractive index from about 1.3 to about 1.7, and one or more higher refractive index materials 40 have a refractive index from about 1.9 to about 3.8. The difference in refractive index between any of the one or more higher refractive index materials 40 and any of the one or more lower refractive index materials 42 may be about 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.5 or more, 2.0 or more, 2.1 or more, 2.2 or more, or even 2.3 or more. Due to the difference in refractive index between the one or more higher refractive index materials 40 and the one or more lower refractive index materials 42, manipulating the number (number) of alternating layers and their thicknesses may result in selective transmission of electromagnetic radiation through window 24 over a range of wavelengths and, separately, selective reflection of electromagnetic radiation from first layered film 36 over a range of wavelengths. The first layered film 36 (and the second layered film 38, if used) is therefore a thin film filter having predetermined optical properties, which are combined based on the amount, thickness, number and materials selected as one or more higher refractive index materials 40 and one or more lower refractive index materials 42.

[0124] Some examples of suitable materials for use as the one or more lower refractive index materials 42 include SiO2, Al2O3, GeO2, SiO, AlO x N y 、SiO x N y 、Si u Al v O x N y , MgO, MgAl2O4, MgF2, BaF2, CaF2, DyF3, YbF3, YF3, and CeF3. The nitrogen content of the material used as the one or more lower refractive index materials 42 can be minimized (for example, in a material such as AlO x N y 、SiO x N y and Si u Al v O x N y of the materials).

[0125] Some examples of suitable materials for use as the one or more higher refractive index materials 40 include Si, amorphous silicon (a-Si), SiN x 、SiN x :H y 、AlN x 、Si u Al v O x N y , Ta2O5, Nb2O5, AlN, Si3N4, AlO x N y 、SiO x N y , HfO2, TiO2, ZrO2, Y2O3, Al2O3, MoO3 and diamond-like carbon. The oxygen content of the material used for the higher refractive index material 40 can be minimized, especially in SiN x or AlN x Materials. AlO x N y The material can be considered as oxygen-doped AlN x , i.e. they may have AlN x The one or more higher refractive index materials 40 may have a crystalline structure (e.g., wurtzite) and need not have an AlON crystalline structure. x N y The material may include from about 0 atomic % to about 20 atomic % oxygen, or from about 5 atomic % to about 15 atomic % oxygen, while including 30 atomic % to about 50 atomic % nitrogen. u Al v O x N y The material may include silicon from about 10 atomic % to about 30 atomic % or from about 15 atomic % to about 25 atomic %, aluminum from about 20 atomic % to about 40 atomic % or from about 25 atomic % to about 35 atomic %, oxygen from about 0 atomic % to about 20 atomic % or from about 1 atomic % to about 20 atomic %, and nitrogen from about 30 atomic % to about 50 atomic %. The foregoing materials may be hydrogenated up to about 30 weight %. Since the refractive indices of the one or more higher refractive index materials 40 and the one or more lower refractive index materials 42 are related to each other, the same material (such as Al2O3) may be appropriate for the one or more higher refractive index materials 40, depending on the refractive index of the material selected for the one or more lower refractive index materials 42, and may alternatively be appropriate for the one or more lower refractive index materials 42, depending on the refractive index of the material selected for the one or more higher refractive index materials 40.

[0126] In an embodiment, the one or more lower refractive index materials 42 of the first layered film 36 are composed of a SiO2 layer, and the one or more higher refractive index materials 40 of the first layered film 36 are composed of a SiO2 layer. x N y or SiN x In an embodiment, the one or more lower refractive index materials 42 of the first layered film 36 are composed of a SiO2 layer, and the one or more higher refractive index materials 40 of the first layered film 36 are composed of a SiN x or SiO x N y and Si (e.g., a-Si) layers, and one or more lower refractive index materials 42 of the second layered film 38 are composed of a SiO2 layer, and one or more higher refractive index materials 40 of the second layered film 38 include SiN x or SiO x N y and a Si (eg, a-Si) layer.

[0127] The number of alternating layers of high refractive index material 40 and low refractive index material 42 in the first layered film 36 or the second layered film 38 is not particularly limited. In an embodiment, the number of alternating layers in the first layered film 36 is 7 or more, 9 or more, 11 or more, 13 or more, 15 or more, 17 or more, 19 or more, 21 or more, 23 or more, 25 or more, or 51 or more, or 81 or more. In an embodiment, the number of alternating layers in the second layered film 38 is 7 or more, 9 or more, 11 or more, 13 or more, 15 or more, 17 or more, 19 or more, 21 or more, 23 or more, 25 or more, or 51 or more, or 81 or more. In an embodiment, the number of alternating layers (excluding substrate 30) of the first layered film 36 and the second layered film 38 that together form the window 24 is 14 or more, 20 or more, 26 or more, 32 or more, 38 or more, 44 or more, 50 or more, 72 or more, or 100 or more. Generally speaking, the greater the number of layers within first layered film 36 and second layered film 38, the more narrowly tuned the transmittance and reflectance characteristics of window 24 are to one or more specific wavelengths or wavelength ranges.

[0128] Each of the alternating layers of the first layered film 36 and the second layered film 38 has a certain thickness. The thickness selected for each of the alternating layers determines the optical path length of light propagating through the window 24, and determines the constructive and destructive interference between different light rays reflected at the various material interfaces of the window 24. Therefore, the thickness of each of the alternating layers, in combination with the refractive index of the one or more higher refractive index materials 40 and the one or more lower refractive index materials 42, determines the reflection and transmission spectra of the window 24.

[0129] refer to Figure 3A, Figure 3B , Figure 4 and Figure 5 , the reflected radiation 28 first encounters the terminal surface 44 of the first layered film 36 when interacting with the window 24, and the terminal surface 44 may be open to the external environment 26. In one embodiment, a layer of the one or more lower refractive index materials 42 provides the terminal surface 44 to more closely match the refractive index of air in the external environment 26 and thereby reduce reflection of incident electromagnetic radiation from the terminal surface 44 (whether reflected radiation 28 or otherwise). The layer of the one or more lower refractive index materials 42 that provides the terminal surface 44 is the layer of the first layered film 36 that is farthest from the substrate 30. Similarly, in an embodiment, when the one or more lower refractive index materials 42 are SiO2, the SiO2 layer is disposed directly onto the first surface 32 of the substrate 30 as the one or more lower refractive index materials 42, which will generally include a large mole percentage of SiO2. Without being bound by theory, it is believed that the commonality of SiO2 in both the substrate 30 and the adjacent layer of the one or more lower refractive index materials 42 achieves increased bonding strength.

[0130] The emitted radiation 22 first encounters the terminal surface 48 of the second layered film 38 when interacting with the window 24. In one embodiment, the layer of the one or more lower refractive index materials 42 provides the terminal surface 48 to more closely match the refractive index of the air within the housing 20 and thereby reduce reflection of the emitted radiation 22 from the terminal surface 48. The layer of the one or more lower refractive index materials 42 that provides the terminal surface 48 is the layer of the second layered film 38 that is farthest from the substrate 30. Similarly, in an embodiment, when the one or more lower refractive index materials 42 are SiO2, the SiO2 layer is disposed directly onto the second surface 34 of the substrate 30 as the one or more lower refractive index materials 42.

[0131] A material having a relatively high refractive index may also have a relatively high hardness, thereby providing scratch resistance and impact resistance. An exemplary material that has both high hardness and can be one of the one or more higher refractive index materials 40 is SiO x N y Other exemplary materials that have both high hardness and can be a relatively high refractive index material 40 are SiN x 、SiN x :H y It has been found that relatively thick (e.g., greater than or equal to 500 nm) SiO x N y(or other suitable higher refractive index material) layer can increase the scratch and / or damage resistance of the window 24. Such increased scratch and / or damage resistance can be particularly beneficial in the first layered film 36 that is more likely to encounter impacts from debris from the external environment 26. Thus, in an embodiment, the first layered film 36 includes a layer of one of the one or more higher refractive index materials 40 having a thickness greater than or equal to 500 nm (e.g., greater than or equal to 1000 nm, greater than or equal to 1500 nm, greater than or equal to 2000 nm). Such a higher refractive index layer having such a thickness of 500 nm or more is described herein as a "scratch resistant layer."

[0132] In embodiments, the thickness of the scratch resistant layer and the location within the first layered film 36 may be optimized to provide a desired level of hardness and scratch resistance to the first layered film 36 and thus the window 24 as a whole. Different applications for the window 24 may result in different desired thicknesses of the scratch resistant layer of the higher refractive index material 40 used as a layer to provide hardness and scratch resistance to the window 24. For example, a window 24 protecting a LIDAR system 12 on a vehicle 10 may require a different thickness of the scratch resistant layer of the higher refractive index material 40 than a window 24 protecting a LIDAR system 12 at an office building. In embodiments, the scratch resistant layer of the higher refractive index material 40 used as a layer to provide hardness and scratch resistance to the window 24 has a thickness between 500 nm and 50,000 nm, such as between 500 nm and 10,000 nm, such as between 2,000 nm and 5,000 nm. In an embodiment, the thickness of this scratch resistant layer of higher refractive index material 40 has a thickness of 50% or more, 65% or more, or 85% or more, or 86% or more of the thickness of the first layered film 36. Generally speaking, the scratch resistant layer of higher refractive index material 40 used as a layer to provide hardness and scratch resistance to window 24 will be part of the first layered film 36 facing the external environment 26, rather than part of the second layered film 38 protected by housing 20, but this may not always be the case.

[0133] As will be described in further detail below, the quantity, thickness, number, and materials of the remaining layers of the first layered film 36 and the second layered film 38 can be configured to provide a window 24 having desired optical properties (transmittance and reflectivity at desired wavelengths) with little regard for the thickness selected for the scratch-resistant layer of the higher refractive index material 40 that serves as a layer providing hardness and scratch resistance to the window 24. This insensitivity of the optical properties of the window 24 as a whole to the thickness of the scratch-resistant layer of the higher refractive index material 40 that serves as a layer providing hardness and scratch resistance to the window 24 occurs when the material has relatively low or negligible optical absorption of electromagnetic radiation at a target wavelength or wavelength range (e.g., 1550 nm from 1400 nm to 1600 nm). For example, Si3N4 only negligibly absorbs electromagnetic radiation in the wavelength range of 700 nm to 2000 nm.

[0134] This general insensitivity allows the scratch-resistant layer of the higher refractive index material 40 in the first layered film 36 to have a thickness that is predetermined to meet a specified hardness or scratch resistance requirement. For example, the first layered film 36 for a window 24 used at the roof 14 of the vehicle 10 may have different hardness and scratch resistance requirements, and thus a different thickness of the scratch-resistant layer of the higher refractive index material 40, than the first layered film 36 for a window 24 used at the front portion 16 of the vehicle 10. This may be achieved without significantly altering the transmittance and reflectance properties of the first layered film 36 as a whole.

[0135] The hardness of the first layered film 36 having a scratch resistant layer of a higher refractive index material 40, and thus the window 24, can be quantified. In embodiments, the maximum hardness of the window 24 measured at the first layered film 36 having a scratch resistant layer of a higher refractive index material 40, as measured by a Bosch indenter hardness test, can be about 8 GPa or greater, about 10 GPa or greater, about 12 GPa or greater, about 14 GPa or greater, about 15 GPa or greater, about 16 GPa or greater, or about 18 GPa or greater at one or more indentation depths from 50 nm to 2000 nm (measured from the terminal surface 44), and even from 2000 nm to 5000 nm. As used herein, the "Bosch indenter hardness test" includes measuring the hardness of a material by pressing a diamond Bosch indenter into the surface on the surface of the material. The Bosch indenter hardness test includes pressing a diamond Bosch indenter into the terminal surface 44 of the first layered film 36 to form an indentation with a depth ranging from about 50 nm to about 2000 nm (or the entire thickness of the first layered film 36), and measuring the maximum hardness of the indentation along the entire indentation depth range or a section of the indentation depth range (for example, in the range from about 100 nm to about 600 nm), which is generally performed using the method described in the following documents: Oliver, WC; Pharr, G. M. An improved technique for determining hardness and elastic modulus using load and displacement sensing indentation experiments. J. Mater. Res., Vol. 7, No. 6, 1992, 1564-1583; and Oliver, W. C.; Pharr, G. M. Measurement of Hardness and Elastic Modulus by Instrument Indentation: Advances in Understanding and Refinements to Methodology. J. Mater. Res., Vol. 19, No. 1, 2004, 3-20. Such hardness levels improve the window 24's ability to function properly in the LIDAR system 12 for its intended purpose, such as with the vehicle 10 (see Figure 1 ) are used with LIDAR systems 12. Thus, these hardness levels reduce or prevent optical scattering and performance degradation of the LIDAR system 12 that would otherwise be caused by impact damage.

[0136] In an embodiment, at least a portion of the first layered film 36 is disposed between the scratch-resistant layer of higher refractive index material 40 and the terminal surface 44. In an embodiment, the first layered film 36 comprises a plurality of alternating layers of one or more lower refractive index materials 42 and one or more higher refractive index materials 40 between the terminal surface 44 and the scratch-resistant layer. Such a stack of alternating layers disposed between the scratch-resistant layer and the terminal surface 44 is described herein as a "light control layer". In an embodiment, the light control layer disposed between the scratch-resistant layer and the terminal surface 44 has a combined thickness greater than or equal to 500 nm (e.g., greater than or equal to 600 nm, greater than or equal to 700 nm, greater than or equal to 800 nm, greater than or equal to 800 nm, greater than or equal to 1000 nm, greater than or equal to 1100 nm, greater than or equal to 1200 nm, greater than or equal to 1300 nm). The number, composition, and thickness of the light control layer may be selected to provide the desired anti-reflection performance attributes described herein at the operating wavelengths of the LIDAR system 12 between 1400 nm and 1600 nm. In this way, the second layered film 38 may be designed to provide the desired optical performance characteristics in the visible and / or UV spectrum, as described herein.

[0137] In an embodiment, at least 25% (e.g., at least 26%, at least 27%, at least 28%, at least 29%, at least 30%) of the thickness 46 of the first layered film 36 is disposed between the scratch resistant layer and the terminal surface 44. It is believed that such depth of the scratch resistant layer within the first layered film 36 promotes the first layered film 36 to have a relatively high nanoindentation hardness (as measured by a Bosch Indenter Hardness Test) over a relatively large depth range within the first layered film 36. In an embodiment, the first layered film 36 has a nanoindentation hardness greater than or equal to 8 GPa from a depth of 250 nm to a depth of 2000 nm within the first layered film 36. In an embodiment, the first layered film 36 has a nanoindentation hardness greater than or equal to 8.5 GPa from a depth of 1000 nm to a depth of 2000 nm within the first layered film 36. Such hardness values ​​promote providing scratch and / or damage resistance against cracks having a relatively wide range of depths.

[0138] Reference now Figure 4 and Figure 5, the first layered film 36 has a thickness 46, and the second layered film 38 has a thickness 50. The thickness 46 of the first layered film 36, which is assumed to be a scratch-resistant layer including one or more higher refractive index materials 40, can be about 1 μm or more, while still providing the transmittance and reflectivity characteristics described herein. In an embodiment, the thickness 46 is in the range of 1 μm to just over 50 μm (including from about 1 μm to about 10 μm and from about 2800 nm to about 5900 nm). The lower limit of about 1 μm is about the minimum value of the thickness 46 that still provides hardness and scratch resistance to the window 24. The upper limit of the thickness 46 is limited by the cost and time required to place the layer of the first layered film 36 on the substrate 30. In addition, the upper limit of the thickness 46 is limited to prevent the first layered film 36 from warping the substrate 30, which depends on the thickness of the substrate 30. The thickness 50 of the second layered film 38 can be any thickness that is considered necessary to impart the desired transmittance and reflectivity characteristics to the window 24. In an embodiment, the thickness 50 of the second layered film 38 is in a range from about 800 nm to about 7000 nm.

[0139] While addressing the issues discussed above in [Background] by imparting hardness, impact resistance, and scratch resistance to window 24 by maximizing the thickness of higher refractive index material 40, the number, thickness, number, and materials of the layers of first layered film 36 and second layered film 38 are configured to also provide relatively high infrared radiation transmittance in a suitable 50 nm wavelength range of interest associated with the sensor system. In an embodiment, the number, thickness, number, and materials of the layers of first layered film 36 and second layered film 38 are configured so that for light normally incident on window 24, window 24 has an average transmittance greater than or equal to 95% (e.g., greater than or equal to 95.5%, greater than or equal to 96.0%, greater than or equal to 96.5%, greater than or equal to 97.0%, greater than or equal to 97.5, greater than or equal to 98%, greater than or equal to 98.5%, greater than or equal to 99%, greater than or equal to 99.5%) in a 50 nm wavelength range of interest included in the 800 nm to 1800 nm wavelength range. In an embodiment, the quantity, thickness, number and material of the layers of the first layered film 36 and the second layered film 38 are configured so that the window 24 has an average reflectivity less than or equal to 5.0% (e.g., less than or equal to 4.5%, less than or equal to 4.0%, less than or equal to 3.5%, less than or equal to 3.0%, less than or equal to 2.5%, less than or equal to 2.0%, less than or equal to 1.5%, less than or equal to 1.0%, less than or equal to 0.5%).

[0140] The specific configuration of the first layered film 36 and the second layered film 38 can vary depending on the wavelength range of interest. For example, in an embodiment, the first layered film 36 and the second layered film 38 can be structured for a 50 nm wavelength range, including a center wavelength of about 905 nm. In such embodiments, the first layered film and the second layered film can generally have the structure described in International Patent Application Publication No. WO 2020 / 247245, entitled "Hardened Optical Windows for LiDAR Applications at 850-950 nm," filed on May 29, 2020, which is hereby incorporated by reference in its entirety.

[0141] In an embodiment, the first layered film 36 and the second layered film 38 may be structured for a 50 nm wavelength range, including a center wavelength of about 1550 nm. In such embodiments, the first layered film and the second layered film may generally have the structure described in International Patent Application Publication No. WO 2020 / 247292, filed on June 1, 2020, entitled "Hardened Optical Windows with Anti-Reflective, Reflective, and Absorbing Layers for Infrared Sensing Systems," which is hereby incorporated by reference in its entirety. In such embodiments, the number, thickness, number, and materials of the layers of the first layered film 36 and the second layered film 38 may be configured so that the window 24 has an average percent reflectivity of less than 10% for electromagnetic radiation having a wavelength of 1550 nm at any incident angle in the range of 0° to 8°.

[0142] By designing the first layered film 36 and the second layered film 38, additional performance attributes (e.g., appearance, optical properties outside of the wavelength range of interest associated with the sensor) can be provided to the window 24. For example, in an embodiment, the first layered film 36 and the second layered film 38 can be configured so that the window 24 exhibits a black or opaque appearance when viewed from the terminal surface 44, and exhibits relatively low transmittance and reflectivity throughout the visible spectrum. In such embodiments, the first layered film 36 and the second layered film 38 can be structured as described in U.S. Provisional Patent Application No. 63 / 344,147, entitled "Hardened Optical Windows with Anti-Reflective Films Having Low Visible Reflectance and Transmission for Infrared Sensing System," filed on May 20, 2022, which is hereby incorporated by reference in its entirety.

[0143] In such embodiments, the thickness, number, and materials of the alternating layers of the first layered film 36 and the second layered film 38 are configured so that for light incident on the first surface 32 and the second surface 34 at an angle within 15° normal to the first surface 32 and the second surface 34, the window 24 has an average reflectivity of less than or equal to 0.5% (e.g., less than or equal to 0.4%, less than or equal to 0.3%, less than or equal to 0.2%, less than or equal to 0.1%, less than or equal to 0.08%) calculated over a 50 nm wavelength range of interest from 1400 nm to 1600 nm. Additionally, in such embodiments, the number, thickness, number, and materials of the alternating layers of the first layered film 36 and the second layered film 38 are configured such that for light incident on the first surface 32 and the second surface 34 at angles within 60° normal to the first surface 32 and the second surface 34 (e.g., at angles of incidence from 0° to 60°, from 0° to 50°, from 0° to 40°, from 0° to 30°), the window has an average P-polarization transmittance and an average S-polarization transmittance calculated over a 50 nm wavelength range of interest from 1400 nm to 1600 nm of greater than 85% (e.g., greater than or equal to 86%, greater than or equal to 87%, greater than or equal to 88%, greater than or equal to 89%, greater than or equal to 90%, greater than or equal to 91%, greater than or equal to 92%). Additionally, in such embodiments, when the light from the external environment 26 (see Figure 2 ), window 24 can exhibit CIELAB color space a* and b* values ​​greater than or equal to -6.0 and less than or equal to 6.0 for light having an incident angle on first surface 32 ranging from 0° to 90° when viewed at an incident angle of less than or equal to 60°. Such color space values ​​can be obtained even in embodiments where substrate 30 has a relatively high transmittance (e.g., greater than 90%) and a relatively low reflectance (e.g., less than or equal to 22%) across the visible spectrum. The thickness, number, and materials of the alternating layers of first layered film 36 and second layered film 38 are configured such that window 24 has a CIELAB lightness L* value less than 45 (e.g., less than or equal to 40, less than or equal to 35, less than or equal to 30) when viewed at an incident angle of less than or equal to 60°.

[0144] In an embodiment, the first layered film 36 and the second layered film 38 are constructed so that when viewed from the terminal surface 44, the window 24 appears transparent. In such embodiments, the first layered film 36 and the second layered film 38 may be structured as described in U.S. Provisional Patent Application No. 63 / 289,828, entitled "Hardened Optical Windows with Anti-Reflective Films Having Low Reflectance and High Transmission in Multiple Spectral Ranges," filed on December 15, 2021, which is hereby incorporated by reference in its entirety. In such embodiments, the thicknesses and materials of the alternating layers of the first layered film 36 and the second layered film 38 are configured so that for light in the visible spectrum incident on the first surface 32 or the second surface 34 at an incident angle of 60° or less, the window 24 has an average percent transmittance greater than or equal to 70% (e.g., greater than or equal to 80%, greater than or equal to 85%). For example, when the external environment 26 (see Figure 1 ), window 24 can exhibit CIELAB color space a* and b* values ​​greater than or equal to -6.0 and less than or equal to 6.0 for light having an incident angle on first surface 32 ranging from 0° to 90° when viewed at a 3D image. Such color space values ​​can be obtained even in embodiments where substrate 30 has a relatively high transmittance (e.g., greater than 90%) and a relatively low reflectance (e.g., less than or equal to 22%) across the entire visible spectrum. In such embodiments, the number, thickness, and materials of the alternating layers of the first layered film 36 and the second layered film 38 are configured such that for light incident on the first surface 32 and the second surface 34 at an angle within 60° normal to the first surface 32 and the second surface 34 (e.g., at an incident angle from 0° to 60°, from 0° to 50°, from 0° to 40°, from 0° to 30°), the window 24 has an average P-polarization transmittance and an average S-polarization transmittance greater than 85% (e.g., greater than or equal to 86%, greater than or equal to 87%, greater than or equal to 88%, greater than or equal to 89%, greater than or equal to 90%) calculated over a 50 nm wavelength range of interest from 1400 nm to 1600 nm.

[0145] In an embodiment, one or more of the first layered film 36 and the second layered film 38 may include one or more transparent conductive oxide layers such that the window 24 exhibits at least 15 dB of microwave energy attenuation for radiation greater than 1 GHz. Alternatively or additionally, in such embodiments, the second layered film 38 may include one or more absorbing layers that are not in direct contact with the substrate 30. Such absorbing layers may not be present in the first layered film 36. In such embodiments, the first layered film 36 and the second layered film 38 may be constructed as described in U.S. Provisional Patent Application No. 63 / 284,161, entitled “Durable Optical Windows for LiDAR Applications,” filed on November 30, 2021.

[0146] The layers of the first layered film 36 and the second layered film 38 (i.e., the high refractive index material layer 40 and the low refractive index material layer 42) can be formed by any method known in the art, including discrete deposition or continuous deposition processes. In one or more embodiments, the layers can be formed using only continuous deposition processes or alternatively only discrete deposition processes.

[0147] Examples

[0148] Exemplary First and Second Layered Films - Exemplary combinations of layered films believed to be suitable for use with the asymmetric laminate structures described herein are provided in Table 3 below. In this example, the first layered film 36 includes twelve (12) SiO2 as the low refractive index material 42 and SiN as the high refractive index material 40. x 36. The first layered film 36 is formed of alternating layers of silicon and a-Si. Layers 7 and 5 of the first layered film 36 are formed of silicon to provide absorptivity in the visible spectrum and also eliminate layers necessary to achieve the desired performance in the infrared. Layers 7 and 5 are also adjacent to other layers of higher refractive index material (e.g., layers 7 and 8 form a combined higher refractive index layer, while layers 4 and 5 form another combined higher refractive index layer). Layer 4 is a scratch resistant layer of higher refractive index material 40 having a thickness of 2000 nm. Thus, the scratch resistant layer is adjacent to the silicon layer to provide a relatively high thickness layer of higher refractive index material. In this example, the scratch resistant layer constitutes 48% of the thickness of the first layered film 36.

[0149] The second layered film 38 includes seven (7) alternating layers of a lower refractive index material 42 and a higher refractive index material 40. In this example, the lower refractive index material 42 is SiO2 and the higher refractive index material 40 is SiN x The lower index material closest to substrate 30 is Si to provide absorptivity in the visible spectrum and reduce the number of layers necessary to achieve desired performance in the infrared.

[0150] The thicknesses of the layers of the first layered film 36 and the second layered film 38 are described in Table 3 below.

[0151]

[0152]

[0153] In another example, for substrate 30, an asymmetric laminate structure 300 is used, wherein the first glass interlayer 200 comprises a 3.8 mm thick borosilicate glass sheet (one of the glasses described in PCT patent application No. PCT / US2021 / 61966 filed on December 6, 2021), the interlayer 330 has a thickness of 0.1 mm and is composed of an optically clear adhesive, and the second glass interlayer 320 is a 0.7 mm thick aluminosilicate glass sheet. In this example, only the first layered film 36 is included.

[0154] Ball bearing impact tests were performed on various laminates that can be used as substrate 30. The first exemplary substrate was a 5.0 mm thick monolithic layer of an existing borosilicate glass composition. The second exemplary substrate was an asymmetric laminate structure 300 in which the first glass interlayer was a 2.85 mm thick unstrengthened aluminosilicate glass layer, the interlayer 330 was a 100 μm thick optically clear adhesive layer, and the second glass interlayer 320 was a 0.55 mm thick unstrengthened aluminosilicate glass layer. The third exemplary substrate was an asymmetric laminate structure 300 in which the first glass interlayer was a 2.85 mm thick unstrengthened aluminosilicate glass layer, the interlayer 330 was a 100 μm thick optically clear adhesive layer, and the second glass interlayer 320 was a 1.1 mm thick chemically strengthened aluminosilicate glass layer. A 1 g ball bearing was projected into the sample on the first glass interlayer 200 (uncoated in this test) at a 45° incident angle. Fig. 6A Depicted is the result of impacting a first exemplary substrate at 80.47 km / hr. As shown, despite the increase in thickness of the substrate, a cone-shaped crack extends through the entire substrate, which will result in a loss of hermeticity. Figure 6B Depicted is the result of impacting a second exemplary substrate at 160.93 km / hr. As shown, a hole is created in the lamination, which will result in a loss of hermeticity. Figure 6C The results of impacting the third exemplary substrate at 160.93 km / h3 are depicted. As shown, the first glass interlayer 200 is broken, but the second glass interlayer 320 is not damaged, so the airtightness is maintained. These results show that the asymmetric laminate structure described herein can provide better impact performance than the monolithic window, even at a smaller total thickness.

[0155] The asymmetric laminate structure 300 was subjected to a pebble gauge test according to ASTM D3170, wherein the first glass interlayer 200 was a 2.85 mm thick non-strengthened aluminosilicate glass and the middle layer 330 was a 760 μm thick acrylic resin ( S15), and the second glass interlayer 320 is a 0.55 mm thick ion exchange strengthened aluminosilicate glass sheet (with low CT-CT10). After two rounds of multiple impact tests, the seal is maintained. Pitting and some cracks are observed on the first glass interlayer 200, but the second glass interlayer 320 is not damaged, so that the airtightness is maintained. The monolithic panel of the same thickness failed to maintain airtightness when subjected to similar tests.

[0156] The light transmittance of four candidate materials for the intermediate layer was measured: (a) 3M TM Optically clear adhesive 8146-1; (b) 3M TM Optically clear adhesive 8214; (c) AA 3491; and (d) S One-component acrylic resin. Figure 7 The results are depicted in . For the individual interlayers, a transmission spectrum between 1520nm and 1580nm is shown. The target is greater than or equal to 98% (and preferably greater than 99%), so that the transmittance of the (uncoated) laminate is greater than 91% (preferably greater than 92%). As shown, each of the interlayers exhibits a transmittance greater than or equal to 98% throughout the depicted wavelength range. The optically clear adhesive exhibits greater than 99% at 1550nm. These results indicate that these interlayer materials are suitable within the reference wavelength range.

[0157] Use about Figure 7 Each of the interlayer materials described constructed an asymmetric laminate structure 300, wherein the first glass interlayer 200 was a 2.85 mm thick unstrengthened aluminosilicate glass layer, the interlayer 330 was 0.1 mm thick, and the second glass interlayer 320 was a 0.55 mm thick chemically strengthened aluminosilicate glass layer. The results are depicted in Table 4 below. vis , R front (reflection from the first major surface 202) and R back (Reflection from the fourth major surface 334) is all average value within the wavelength range of 380nm to 780nm. 940 and T 1550 The transmittance at wavelengths of 940 nm and 1550 nm, respectively. All values ​​are percentages and are measured at normal incidence.

[0158] Table 4

[0159]

[0160] It is believed that the presence of at least one of the first layered film 36 and the second layered film 38 described herein (such as in the examples in Table 4) will increase the transmittance value by at least 6% and decrease the reflectance value by at least 6% (when the second layered film 38 is included). Therefore, the above results show that the coating lamination according to the present disclosure is capable of exhibiting an average transmittance of at least 95% within a 50 nm wavelength range included in the 800 nm to 1800 nm wavelength range and an average reflectance of less than 5% within the 50 nm wavelength range.

[0161] It will be apparent to those skilled in the art that various modifications and variations can be made without departing from the spirit and scope of the claims.

Claims

1. A window for a sensing system, comprising: a first glass interlayer, the first glass interlayer comprising a first major surface, a second major surface opposite the first major surface, and a first thickness extending between the first major surface and the second major surface; a second glass interlayer, the second glass interlayer comprising a third major surface, a fourth major surface opposite the third major surface, and a second thickness extending between the third major surface and the fourth major surface; an interlayer disposed between the first glass interlayer and the second glass interlayer and bonding the second major surface to the third major surface; and one or more layered films disposed on at least one of the first major surface and the fourth major surface, each of the one or more layered films comprising alternating layers of one or more higher refractive index materials and one or more lower refractive index materials, wherein: The intermediate layer alone comprises an average transmittance greater than 98% over a 50 nm wavelength range of interest for light normally incident on the fourth major surface or the first major surface, The 50 nm wavelength range of interest is contained within the wavelength range of 800 nm to 1800 nm, The alternating layers of the one or more layered films are configured such that the window exhibits an average transmittance greater than or equal to 95% over the 50 nm wavelength range of interest for light normally incident on the first major surface or the fourth major surface, The alternating layers of the one or more layered films are configured such that the window exhibits an average reflectivity of less than or equal to 5% over the 50 nm wavelength range of interest for light normally incident on the first major surface or the fourth major surface, The first thickness is at least twice the second thickness, and The second glass interlayer is strengthened to a greater extent than the first glass interlayer, such that the second glass interlayer exhibits a central tension in a central region thereof that is greater than a central tension of the first glass interlayer.

2. The window of claim 1, wherein the first glass interlayer is unstrengthened.

3. A window as claimed in any one of the preceding claims, wherein: The first thickness is greater than or equal to 2.0 mm and less than or equal to 8.0 mm, and The second thickness is greater than or equal to 0.1 mm and less than or equal to 1.2 mm.

4. The window of any one of the preceding claims, wherein both the first glass interlayer and the second glass interlayer are formed of aluminosilicate glass.

5. The window of any one of claims 1-3, wherein the first glass interlayer is formed from a glass that exhibits abnormal fracture behavior when subjected to a Vickers indenter test.

6. The window of claim 5, wherein the first glass interlayer comprises a borosilicate glass composition.

7. The window of claim 6, wherein: In terms of constituent oxides, the borosilicate glass composition comprises: SiO2, B2O3, Al2O3, one or more alkali metal oxides and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO and ZnO, 11 mol% or more and 16 mol% or less of B2O3, 2 mol % or more and 6 mol % or less of Al2O3 and The total amount of Na2O, K2O, MgO and CaO is greater than or equal to 7.0 mol%, The concentrations in molar percentage on the oxide basis of SiO2, B2O3, the one or more alkali metal oxides, Al2O3 and the one or more alkaline earth metal oxides satisfy the following relationship: (R2O+R'O)≥A12O3, 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, and wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides.

8. The window of any one of the preceding claims, wherein the first thickness is at least 3 times the second thickness.

9. The window of any of the preceding claims, wherein the second glass interlayer is chemically strengthened such that the second glass interlayer comprises a surface compressive stress at the fourth major surface greater than or equal to 250 MPa and less than or equal to 900 MPa.

10. The window of claim 9, wherein when the first glass interlayer is subjected to a 1g ball bearing impact traveling at 160.93 km / hr, no cracks extending through the entire second thickness are formed.

11. The window of any one of the preceding claims, wherein the interlayer comprises an optically clear adhesive or a UV curable acrylate resin. 12 . The window of claim 11 , wherein the intermediate layer comprises a third thickness greater than or equal to 0.05 mm and less than or equal to 1.0 mm.

13. The window of any one of claims 1-12, wherein the 50 nm wavelength range of interest is centered around wavelengths between 900 nm and 950 nm.

14. The window of any one of claims 1-12, wherein the 50 nm wavelength range of interest is centered around wavelengths between 1525 nm and 1575 nm.

15. A window as claimed in any preceding claim, wherein: The one or more layered films include a first layered film disposed on the first major surface, and The window comprises a maximum hardness of at least 8 GPa at the first layered film and as measured by a Bohr indenter hardness test.

16. The window of claim 15, wherein: The one or more layered films include a second layered film disposed on the fourth major surface, and The quantity, thickness, number and material of the alternating layers of the first layered film and the second layered film are configured such that: the window having an average reflectivity of less than 0.5% calculated over the 50 nm wavelength range of interest between 1400 nm and 1600 nm for light incident on the first and second surfaces at an angle of less than or equal to 15°; The window has a CIELABL* value of less than or equal to 45 for an angle of incidence of less than or equal to 60° on the first layered film; and When viewed from a side of the first layered film, the window has CIELA Ba* and b* values ​​greater than or equal to -6.0 and less than or equal to 6.

0.

17. The window of claim 16, wherein: One of the alternating layers of the first layered film that is furthest from the first major surface forms a terminal surface material of the window, the terminal surface material of the window comprising the lower refractive index material, and The first layered film includes a scratch resistant layer formed of one of the one or more higher refractive index materials and having a thickness greater than or equal to 1500 nm and less than or equal to 5000 nm.

18. The window of claim 17, wherein: The scratch resistant layer is separated from the terminal surface by a plurality of the alternating layers of the one or more lower refractive index materials and the one or more higher refractive index materials of the first layered film, and The scratch resistant layer is separated from the terminal surface by at least 1000 nm.

19. The window of claim 15, wherein: The one or more layered films include a second layered film disposed on the fourth major surface, and The number, thickness and materials of the alternating layers of the first layered film and the second layered film are configured such that: The window has an average percent transmittance greater than 90% calculated over the 50 nm wavelength range of interest for light incident on the first surface and the second surface at an angle of incidence less than or equal to 15°; The window has an average reflectivity of less than 0.5% calculated over the 50 nm wavelength range of interest for light incident on the first and second surfaces at angles less than or equal to 15°; and The window has an average percent transmittance greater than 80% calculated from 400 nm to 700 nm for light incident on the first and second surfaces at an angle of incidence less than or equal to 15°.

20. A window for a sensing system, the window comprising: a first glass interlayer, the first glass interlayer comprising a first major surface, a second major surface opposite the first major surface, and a first thickness extending between the first major surface and the second major surface; a second glass interlayer, the second glass interlayer comprising a third major surface, a fourth major surface opposite the third major surface, and a second thickness extending between the third major surface and the fourth major surface; an interlayer disposed between the first glass interlayer and the second glass interlayer and bonding the second major surface to the third major surface; and one or more layered films disposed on at least one of the first major surface and the fourth major surface, each of the one or more layered films comprising alternating layers of one or more higher refractive index materials and one or more lower refractive index materials, wherein: The first glass interlayer, the second glass interlayer and the interlayer in combination, without the one or more layered films, comprise an average transmission greater than 90% in a 50 nm wavelength range of interest, The 50 nm wavelength range of interest is contained within the wavelength range of 800 nm to 1800 nm, The alternating layers of the one or more layered films are configured such that the window exhibits an average transmittance greater than or equal to 95% over the 50 nm wavelength range of interest for light normally incident on the first major surface or the fourth major surface, The alternating layers of the one or more layered films are configured such that the window exhibits an average reflectivity of less than or equal to 5% over the 50 nm wavelength range of interest for light normally incident on the first major surface or the fourth major surface, The first thickness is at least twice the second thickness, and The second glass interlayer is strengthened to a greater extent than the first glass interlayer, such that the second glass interlayer exhibits a central tension in a central region thereof that is greater than a central tension of the first glass interlayer.

21. The window of claim 20, wherein the first glass interlayer is unstrengthened.

22. The window of any one of claims 20-21, wherein: The first thickness is greater than or equal to 2.0 mm and less than or equal to 8.0 mm, and The second thickness is greater than or equal to 0.1 mm and less than or equal to 1.2 mm.

23. The window of any one of claims 20-22, wherein both the first glass interlayer and the second glass interlayer are formed of aluminosilicate glass.

24. The window of any one of claims 20-23, wherein the first glass interlayer is formed from a glass that exhibits abnormal fracture behavior when subjected to a Vickers indenter test.

25. The window of claim 24, wherein the first glass interlayer comprises a borosilicate glass composition.

26. The window of claim 25, wherein: In terms of constituent oxides, the borosilicate glass composition comprises: SiO2, B2O3, Al2O3, one or more alkali metal oxides and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO and ZnO, greater than or equal to 11 mol % and less than or equal to 16 mol % B2O3, 2 mol % or more and 6 mol % or less of Al2O3 and The total amount of Na2O, K2O, MgO and CaO is greater than or equal to 7.0 mol%, The concentrations in molar percentage on the oxide basis of SiO2, B2O3, the one or more alkali metal oxides, Al2O3 and the one or more alkaline earth metal oxides satisfy the following relationship: (R2O+R'O)≥A12O3, and 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides.

27. The window of any one of claims 20-26, wherein the first thickness is at least 3 times the second thickness.

28. The window of any one of claims 20-27, wherein the second glass interlayer is chemically strengthened such that the second glass interlayer comprises a surface compressive stress at the fourth major surface that is greater than or equal to 250 MPa and less than or equal to 900 MPa.

29. The window of claim 28, wherein when the first glass interlayer is subjected to a 1g ball bearing impact traveling at 160.93 km / hr, no cracks extending through the entire second thickness are formed.

30. The window of any one of claims 20-29, wherein the interlayer comprises an optically clear adhesive or a UV curable acrylate resin.

31. The window of claim 30, wherein the intermediate layer comprises a third thickness greater than or equal to 0.05 mm and less than or equal to 1.0 mm.

32. The window of any one of claims 20-31, wherein the 50 nm wavelength range of interest is centered around wavelengths between 900 nm and 950 nm.

33. The window of any of claims 20-31, wherein the 50 nm wavelength range of interest is centered around wavelengths between 1525 nm and 1575 nm.

34. The window of any one of claims 20 to 33, wherein: The one or more layered films include a first layered film disposed on the first major surface, and The window comprises a maximum hardness of at least 8 GPa at the first layered film and as measured by a Bohr indenter hardness test.

35. The window of claim 34, wherein: The one or more layered films include a second layered film disposed on the fourth major surface, and The quantity, thickness, number and material of the alternating layers of the first layered film and the second layered film are configured such that: the window having an average reflectivity of less than 0.5% calculated over the 50 nm wavelength range of interest between 1400 nm and 1600 nm for light incident on the first and second surfaces at an angle of less than or equal to 15°; The window has a CIELABL* value of less than or equal to 45 for an angle of incidence of less than or equal to 60° on the first layered film; and When viewed from a side of the first layered film, the window has CIELA Ba* and b* values ​​greater than or equal to -6.0 and less than or equal to 6.

0.

36. The window of any one of claims 35, wherein: One of the alternating layers of the first layered film that is furthest from the first major surface forms a terminal surface material of the window, the terminal surface material of the window comprising the lower refractive index material, and The first layered film includes a scratch resistant layer formed of one of the one or more higher refractive index materials and having a thickness greater than or equal to 1500 nm and less than or equal to 5000 nm.

37. The window of claim 36, wherein: The scratch resistant layer is separated from the terminal surface by a plurality of the alternating layers of the one or more lower refractive index materials and the one or more higher refractive index materials of the first layered film, and The scratch resistant layer is separated from the terminal surface by at least 1000 nm.

38. The window of claim 34, wherein: The one or more layered films include a second layered film disposed on the fourth major surface, and The number, thickness and material of the alternating layers of the first layered film and the second layered film are configured such that: The window has an average percent transmittance greater than 90% calculated over the 50 nm wavelength range of interest for light incident on the first surface and the second surface at an angle of incidence less than or equal to 15°; The window has an average reflectivity of less than 0.5% calculated over the 50 nm wavelength range of interest for light incident on the first and second surfaces at angles less than or equal to 15°; and The window has an average percent transmittance greater than 80% calculated from 400 nm to 700 nm for light incident on the first and second surfaces at an angle of incidence less than or equal to 15°.

39. A sensor system, the sensor system comprising: an emitter that emits radiation within a 50 nm wavelength range of interest, the 50 nm wavelength range of interest being contained within a wavelength range from 800 nm to 1800 nm; a sensor configured to detect the radiation emitted by the emitter; a housing defining a sensor cavity, wherein the transmitter and the sensor are received in the sensor cavity; and A window as claimed in any one of claims 21-38, wherein the window is attached to the housing to hermetically seal the sensor cavity.

40. The sensor system of claim 39, wherein the second glass interlayer comprises a dimension greater than a dimension of the first glass interlayer, and the second glass interlayer is attached to the housing such that the first major surface is flush with a front surface of the housing.

41. The sensor system of claim 40, wherein the sensor cavity remains hermetically sealed after impacting the window with a 1 g ball bearing traveling at 160.9 s km / hr at an incident angle of 45°.

Citation Information

Patent Citations

  • Glass with unique fracture behavior for vehicle windshield

    US11951713B2

  • Hardened optical windows for lidar applications at 850-950nm

    WO2020247245A1

  • Hardened optical windows with Anti-reflective, reflective, and absorbing layers for infrared sensing systems

    WO2020247292A1

  • Asymmetric glass laminates

    CN108430767A

  • Hardened optical windows for lidar applications at 850-950nm

    CN113906318A